Bioaccumulation of trace elements by Leach's storm-petrels (Hydrobates leucorhous) in the North and South Atlantic Ocean during the non-breeding period - Catherine Potvin; Manon Sorais; Robert A. Ronconi; Katharine R. Studholme; April Hedd; Alexander L. Bond; Vegard S. Bråthen; Sydney M. Collins; Laura Crick; Joshua T. Cunningham; Anne N.M.A. Ausems; David A. Fifield; et al. (Marine Pollution Bulletin, 2026)

Waste heat recovery from a retrofitted generator using a thermoelectric generator (TEG) - Collins N. Nwaokocha; Daniel J. Poheto; Abayomi T. Layeni; Amos B. Ogunfowora; Olanrewaju S. Olasanmi; Oguntola J. Alamu; Mohsen Sharifpur (Next Research, 2026)

White wine, sparkling white wine and black caviar – The sensory experience of pairing of flavours - K. Wendin; B. Collin; S. Forsberg; H. Scander; R. Albin; F. Åhrberg; T. Ranta (International Journal of Gastronomy and Food Science, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Non-destructive sampling of larval amphibians shows tail tissues reflect whole-body methylmercury concentrations and trophic-related differences in bioaccumulation - Brian J. Tornabene; Blake R. Hossack; Daniel A. Grear; Thomas L. Anderson; Brad M. Glorioso; J. Hardin Waddle; Jon M. Davenport; Collin A. Eagles-Smith; Caitlin T. Rumrill; Kelly L. Smalling (Ecotoxicology, 2026)
Mercury (Hg), and specifically methylmercury (MeHg), is a contaminant of global concern to humans and wildlife, but there is still limited understanding of its effects on many taxa. Amphibians are closely associated with water, where Hg is converted to MeHg, and high concentrations of MeHg can reduce survival of amphibians in the wild. However, limited non-lethal proxies exist for estimating MeHg bioaccumulation in amphibian larvae, which could be used to reduce destructive sampling and allow sampling of imperiled species. We evaluated whether tail clips were indicative of whole-body MeHg concentrations of larval amphibians, whether dragonflies were an effective bioindicator of Hg concentrations of larval amphibians, and compared MeHg bioaccumulation in predatory caudate (salamanders, newts) and non-predatory anuran (frogs, toads) larvae. Tail-clip and whole-body MeHg concentrations were strongly correlated, especially for caudates. There was high variability among sites and species, but caudates had higher MeHg than anurans, and MeHg concentrations of caudates and anurans were strongly correlated. Dragonflies were a weak indicator of MeHg for anurans but strong indicators for larval caudates, likely because caudates and dragonflies are carnivorous and occupy similar trophic positions. Our study revealed that sampling tails can be an effective non-destructive index of whole-body MeHg for larval amphibians and demonstrates differences in MeHg bioaccumulation related to trophic position in larval amphibians and dragonflies. All post-embryo life stages for a broad suite of amphibian species can now be sampled non-lethally for MeHg, allowing for a broader examination of population-level effects and focus on imperiled species that cannot be sampled destructively.

Timing of exposure impacts how organophosphorus pesticides affect the developing brain in the planarian Dugesia japonica - Rebecca T. Somach; Danielle Ireland; Hao P. Tran; Gustav Allotey; Eva-Maria S. Collins (Archives of Toxicology, 2026)
Exposure to organophosphorus pesticides (OPs) during pregnancy has been suggested to cause adverse outcomes on neural development of the fetus but the mechanisms underlying developmental neurotoxicity of OPs remain unclear. While OPs share acetylcholinesterase (AChE) as the primary molecular target, different OPs have been shown to induce different effects in laboratory studies. Previously, we found that OPs differentially affect regenerating planarians when applied on the first day of regeneration. To determine if the timing of OP exposure affects adverse outcomes, here, we performed a comparative study of 5 OPs—chlorpyrifos (17.8 μM), diazinon (16.2 μM), dichlorvos (1 μM), profenofos (10 μM), and malathion (56.2 μM)—in the planarian Dugesia japonica . We evaluated how effects on behavior and nervous system morphology changed with OP exposure starting on different days of regeneration/development. We found that some toxic effects were dependent on the developmental stage during exposure. For example, profenofos impaired brain development when exposure started on day 1 of development but caused lethality when exposure started during later stages. Inhibition of the enzymatic activity of AChE on day 12 of exposure was not affected by the different exposure paradigms, suggesting that the differential effects were either due to effects on the non-enzymatic functions of AChE or on other targets during neurodevelopment. This work provides insight into which neurodevelopmental key events are affected by OP exposure, enabling future mechanistic work to identify the targets underlying OP developmental neurotoxicity.

Nutrient Enrichment Increases Grassland Biomass Sensitivity to Interannual Precipitation Variation - Ingrid J. Slette; Eric W. Seabloom; Carlos Alberto Arnillas; Jonathan D. Bakker; Dana Blumenthal; Jane A. Catford; Scott L. Collins; Nico Eisenhauer; Philip A. Fay; Magda Garbowski; Sylvia Haider; W. Stanley Harpole; et al. (Global Change Biology, 2026)
Primary production underpins much of ecosystem functioning and is often limited by nutrient and water availability. Ongoing global increases in nutrient inputs and interannual precipitation variability are thus likely to impact primary production, with unclear consequences for interannual variability in plant biomass. We used data from 35 grasslands in the Nutrient Network coordinated fertilization experiment to test if nutrient addition alters the response of plant biomass to year‐to‐year variation in growing season precipitation, and whether the effects of nutrient addition vary with factors such as site aridity or plant community composition. Nutrient addition increased biomass (by an average of 46% across sites), rain‐use efficiency (by 48%), and the sensitivity of biomass to interannual variation in precipitation (i.e., larger increase in biomass in wet years; by 13%), but did not change the strength of the interannual precipitation‐biomass correlation. Both sensitivity and correlation strength were higher in more arid sites, regardless of nutrient addition. These results suggest that grassland ecosystem functioning may become more variable from year to year as nutrient enrichment increases biomass sensitivity to precipitation and precipitation becomes more variable.

Effect of temperature on membrane lipids of Pseudomonas veronii isolated from French alpine lakes - Juanita Mora-Gomez; Sylvie Collin; Adrienne Kish; Christelle Anquetil; Marcelino T Suzuki; Pierre Sabatier; Emmanuel Malet; William Rapuc; Céline Begorre; Mathieu Dellinger; Arnaud Huguet (Organic Geochemistry, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

The greater McArthur Basin: introduction to the Australian Journal of Earth Sciences Special Volume - A. S. Collins; T. Blaikie (Australian Journal of Earth Sciences, 2026)

The detrital zircon record of the Mesoproterozoic Renner Group, Tomkinson Province, northern Australia: correlations within the greater McArthur Basin - M. L. Blades; T. J. Munson; A. de Groot; A. S. Collins; D. Subarkah; A. Nixon; B. Yang (Australian Journal of Earth Sciences, 2026)

Toxicity of polycaprolactone nanoplastics, pristine or weathered in environmental conditions, to human intestinal epithelial cells, in vitro - M. Boulée; V. Bard; M. Papin; D. Béal; S. Devineau; D. Fenel; E. Dusacq; V. Collin-Faure; T. Rabilloud; T. Douki; M. Carriere (NanoImpact, 2026)

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Precipitation variability interacts with mean precipitation to restructure a semiarid grassland community - Jennifer A. Rudgers; Laureano A. Gherardi; Purbendra Yogi; Melissa Bacigalupa; Tom E. X. Miller; Jacob J. Blais; Lana Bolin; Scott L. Collins; Enqing Hou; Yiqi Luo; Javier O. Morales; William T. Pockman; et al. (Ecology, 2026)
Climate forecasts project change not only in the mean of climate variables but also in their variance. If these dual changes interact, then future ecological dynamics will be difficult to predict using current experimental approaches, which typically change the mean or impose a single extreme event, such as drought. We designed a new field experiment to factorially reduce mean precipitation and increase its interannual variability. Across 4 years, drier, more variable precipitation additively reduced aboveground primary productivity by 48%–69% and interactively reduced the dominant plant species, but had no effect on the plant species predicted to dominate in the future, which could lead to state transition. Drier, more variable precipitation also interactively reduced biodiversity more than either climate factor alone, with 37%–42% fewer plant species than under ambient conditions, a pattern that matched declining richness during the past 20 years of ongoing climate change. Drier, more variable precipitation restructured the composition and spatiotemporal variation of the plant community. Altered precipitation mean or variance affected 14% of plant species, with eight species sensitive to the mean × variance interaction. Results suggest that future forecasts of plant community structure may be inadequate if they fail to incorporate climate mean × variance interactions.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Central American Mangrove Blue Carbon: Distribution, Dynamics and Future Directions - Nicholas T. Girkin; Steven W. J. Canty; Andre S. Rovai; Hannah K. Morrissette; Rachel Collin; Yashvini Shukla; Tania E. Romero-González; Jose Quirós; Jorge Pineda; Jacklyn Rivera Wong; Miguel Cifuentes-Jara (Wetlands, 2026)
Mangroves are one of the most important Blue Carbon ecosystems within the tropics and subtropics, capturing and storing more atmospheric carbon dioxide per unit area than terrestrial forest systems. There is large variation in estimates of carbon stocks of mangroves in Central America, due to differences in underlying geomorphology, localised environmental conditions, and species composition, which also vary between the Pacific and Atlantic coastlines. In this review, we assess our current knowledge of the distribution of mangroves in the region, their role as a carbon sink, our current understanding of their dynamics and resilience, and identify key questions to understand their likely responses to future environmental change processes. This is of particular concern as the Central American region is predicted to experience significant climatic changes, such as increased air and sea surface temperatures, greater frequencies of high intensity cyclones, and increased drought events. Understanding the resilience and vulnerability of these systems will have policy and management implications for the role of Blue Carbon ecosystems as natural climate solutions, ecosystem-based adaptation plans, and disaster risk reduction strategies.

Drought, topography, and forest management shape wildfire occurrence and severity in montane Australian landscapes - Jeremy Johnson; Luke T. Kelly; Luke Collins; Stephen Stewart; Craig R. Nitschke (Science of The Total Environment, 2025)

Factors affecting short-term post-release survival probability of Lake Trout implanted with acoustic telemetry transmitters - Alexander J. Gatch; Dimitry Gorsky; Kyle T. Morton; R. Josephine Johnson; Collin J. Farrell; Timothy B. Johnson; Emma J. Bloomfield; Brent Metcalfe; Jessica Goretzke; Michael Connerton; Sarah M. Larocque; Jonathan D. Midwood; et al. (Fisheries Research, 2025)

Linking soil-metal concentrations with children's blood and urine biomarkers in Syracuse, NY - Dustin T. Hill; Michael Petroni; Vikrant Jandev; Kestutis Bendinskas; Lynn S. Brann; James A. MacKenzie; Christopher D. Palmer; Patrick J. Parsons; Mary B. Collins; Brooks B. Gump (Environmental Research, 2025)

Precipitation‐productivity relationships in desert grassland: A test of the double asymmetry hypothesis - Scott L. Collins; Mariah T. Patton; Renée F. Brown (Ecology, 2025)
Understanding the relationship between precipitation (PPT) and aboveground net primary productivity (ANPP) is essential for modeling the global carbon cycle. Across grassland to forest gradients, the PPT‐ANPP relationship is well defined and nonlinear. Temporal patterns within a site over time are more variable and nearly always linear. Linear relationships, however, are inconsistent with positive asymmetry, where increases in ANPP during wet years exceed declines in dry years. The double asymmetry model predicts that concave‐down nonlinearities will occur when extreme high and low PPT years are included in a time series. We tested this prediction using long‐term observational ANPP data along with rainfall manipulation experiments. By combining observational records with experimental treatments, including drought, water addition, and nitrogen addition, we found some support for the double asymmetry model. However, the response under high precipitation coupled with nitrogen addition was concave‐up, not down. By experimentally extending the range of monsoon precipitation, we found a weak but significant, nonlinear PPT‐ANPP relationship, but only when nutrient limitation was alleviated. Our results demonstrate that multiple interacting factors govern the PPT‐ANPP relationship within a site over time, challenging our ability to predict how ANPP will respond to changes in precipitation in the future.

Nutrient limitation dampens the response of a harmful algae to a marine heatwave in an upwelling system - Alexis D. Fischer; Emilie Houliez; Brian D. Bill; Maria T. Kavanaugh; Simone R. Alin; Andrew U. Collins; Raphael M. Kudela; Stephanie K. Moore (Limnology and Oceanography, 2025)
Harmful algal blooms caused by toxin‐producing species of the diatom genus Pseudo‐nitzschia have been linked to anomalously warm ocean conditions in the Northern California Current System. This study compares summertime concentrations of Pseudo‐nitzschia spp. and the toxin they produce, domoic acid, during a marine heatwave year (2019) and a climatologically neutral year (2021). An Imaging FlowCytobot was installed on a fishery survey vessel alongside environmental sensors to continuously sample phytoplankton and oceanographic parameters. This was paired with targeted manual sample collections for nutrients, chlorophyll, and domoic acid. Accumulations of Pseudo‐nitzschia spp. were associated with upwelling zones and established hotspot regions: the Juan de Fuca Eddy, Heceta Bank, and Trinidad Head. Overall, however, Pseudo‐nitzschia spp. and domoic acid concentrations were low during both summers and appear to have been limited by nitrate. Nutrient availability may therefore modulate the response of Pseudo‐nitzschia spp. to warm anomalies. Comparison of these results with 2015, another marine heatwave year but one that produced record concentrations of Pseudo‐nitzschia spp. and domoic acid, suggests that the timing of marine heatwave conditions in the nearshore relative to seasonal upwelling plays a key role in determining whether a Pseudo‐nitzschia spp. harmful algal bloom will occur.

Fitness incentives to male fighters undermine fighting performance in intergroup contests - P.A. Green; D.W.E. Sankey; T. Collins; F. Mwanguhya; H.J. Nichols; M.A. Cant; F.J. Thompson (Animal Behaviour, 2025)

Carbon inventories: New opportunities and challenges for agriculture and forestry - Júnior Melo Damian; Carlos Eduardo Pellegrino Cerri; Luís Gustavo Barioni; Maurício Roberto Cherubin; Martial Bernoux; Richard T. Conant; Marcelo Valadares Galdos; Adrian L. Collins (CATENA, 2025)

Assessment of an indirect fluorescent antibody test for the detection of antibodies specific for Pajaroellobacter abortibovis in adult cattle - Myra T. Blanchard; Kassidy M. Collins; Jeffrey L. Stott (Veterinary Immunology and Immunopathology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Tundra Vegetation Community Type, Not Microclimate, Controls Asynchrony of Above‐ and Below‐Ground Phenology - Elise C. Gallois; Isla H. Myers‐Smith; Colleen M. Iversen; Verity G. Salmon; Laura L. Turner; Ruby An; Sarah C. Elmendorf; Courtney G. Collins; Madelaine J. R. Anderson; Amanda Young; Lisa Pilkinton; Gesche Blume‐Werry; et al. (Global Change Biology, 2025)
The below‐ground growing season often extends beyond the above‐ground growing season in tundra ecosystems and as the climate warms, shifts in growing seasons are expected. However, we do not yet know to what extent, when and where asynchrony in above‐ and below‐ground phenology occurs and whether variation is driven by local vegetation communities or spatial variation in microclimate. Here, we combined above‐ and below‐ground plant phenology metrics to compare the relative timings and magnitudes of leaf and fine‐root growth and senescence across microclimates and plant communities at five sites across the Arctic and alpine tundra biome. We observed asynchronous growth between above‐ and below‐ground plant tissue, with the below‐ground season extending up to 74% (~56 days) beyond the onset of above‐ground leaf senescence. Plant community type, rather than microclimate, was a key factor controlling the timing, productivity, and growth rates of fine roots, with graminoid roots exhibiting a distinct ‘pulse’ of growth later into the growing season than shrub roots. Our findings indicate the potential of vegetation change to influence below‐ground carbon storage as the climate warms and roots remain active in unfrozen soils for longer. Taken together, our findings of increased root growth in soils that remain thawed later into the growing season, in combination with ongoing tundra vegetation change including increased shrub and graminoid abundance, indicate increased below‐ground productivity and altered carbon cycling in the tundra biome.

A male-killing Spiroplasma endosymbiont has age-mediated impacts on Drosophila endurance and sleep - Collin J. Horn; Sissi Yuli; Jacob A. Berry; Lien T. Luong (Journal of Insect Physiology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Ecology of eyetail bowfin (Amia ocellicauda) in Green Bay, Lake Michigan - Collin Moratz; Jeremiah S. Shrovnal; Amelia T. McReynolds; Christopher Houghton; Patrick S. Forsythe (Environmental Biology of Fishes, 2024)

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

A review of lithogeochemical dispersion haloes of LCT pegmatites, and their application to rare metal exploration, with special reference to lithium in an Australian context - M. T. Sweetapple; P. J. Vanstone; G. R. Lumpkin; P. L. F. Collins (Australian Journal of Earth Sciences, 2024)

Offshore windfarm construction elevates metabolic rate and increases predation vulnerability of a key marine invertebrate - Seth F. Cones; Youenn Jézéquel; Sierra Jarriel; Nadège Aoki; Hannah Brewer; John Collins; Laurent Chauvaud; T. Aran Mooney (Environmental Pollution, 2024)

Long-term trends in study duration of lakes and reservoirs over recent decades - T. M. Detmer; S. F. Collins; D. H. Wahl (Hydrobiologia, 2024)

Eight weeks of high-intensity interval training versus stretching do not change the psychoneuroendocrine response to a social stress test in emotionally impulsive humans - F. Javelle; W. Bloch; U. Borges; T. Burberg; B. Collins; N. Gunasekara; T. J. Hosang; T. Jacobsen; S. Laborde; A. Löw; A. Schenk; M. L. Schlagheck; et al. (European Journal of Applied Physiology, 2024)
Purpose Research supports physical activity as a method to heighten stress resistance and resilience through positive metabolic alterations mostly affecting the neuroendocrine system. High-intensity interval training (HIIT) has been proposed as a highly effective time-saving method to induce those changes. However, existing literature relies heavily on cross-sectional analyses, with few randomised controlled trials highlighting the necessity for more exercise interventions. Thus, this study aims to investigate the effects of HIIT versus an active control group on the stress response to an acute psychosocial stressor in emotionally impulsive humans (suggested as being strong stress responders). Methods The study protocol was registered online (DRKS00016589) before data collection. Sedentary, emotionally impulsive adults (30.69 ± 8.20 y) were recruited for a supervised intervention of 8 weeks and randomly allocated to either a HIIT ( n = 25) or a stretching group ( n = 19, acting as active controls). Participants were submitted to a test battery, including saliva samples, questionnaires (self-efficacy- and perceived stress-related), visual analogue scales (physical exercise- and stress-related), and resting electroencephalography and electrocardiography assessing their reaction to an acute psychological stressor (Trier Social Stress Test) before and after the exercise intervention. Results HIIT increased aerobic fitness in all participants, whereas stretching did not. Participants from the HIIT group reported perceiving exercising more intensively than those from the active control group ( ƞ p 2 = 0.108, p = 0.038). No further group differences were detected. Both interventions largely increased levels of joy post-TSST ( ƞ p 2 = 0.209, p = 0.003) whilst decreasing tension ( ƞ p 2 = 0.262, p < 0.001) and worries ( ƞ p 2 = 0.113, p = 0.037). Finally, both interventions largely increased perceived levels of general self-efficacy ( ƞ p 2 = 0.120, p = 0.029). Conclusion This study suggests that 8 weeks of HIIT does not change the psychoneuroendocrine response to an acute psychological stress test compared to an active control group in emotionally impulsive humans. Further replications of supervised exercise studies highly powered with active and passive controls are warranted.

P06-18 Enhancing prediction and priorisation of adverse effects: TOXsIgN as a comprehensive resource for toxicogenomics - T. Darde; I. Kugathas; M. Boudet; A. Bretaudeau; R. Le Guével; L. Noël; T. Svingen; O. Collin; A. Rolland; F. Chalmel (Toxicology Letters, 2024)

Pre- and post-flowering impacts of natural heatwaves on yield components in wheat - Najeeb Ullah; Brian Collins; John T. Christopher; Troy Frederiks; Karine Chenu (Field Crops Research, 2024)

Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

Protective immunity induced through two calving seasons following administration of live epizootic bovine abortion agent (EBAA) vaccine - Myra T. Blanchard; Mike B. Teglas; Kassidy M. Collins; Mark L. Anderson; Bret R. McNabb; Jeffrey L. Stott (Veterinary Immunology and Immunopathology, 2024)

Indoor and ambient black carbon and fine particulate matter associations with blood biomarkers in COPD patients - Cathy L. Zhang; Jennifer R. Maccarone; Stephanie T. Grady; Christina M. Collins; Marilyn L. Moy; Jaime E. Hart; Choong-Min Kang; Brent A. Coull; Joel D. Schwartz; Petros Koutrakis; Eric Garshick (Science of The Total Environment, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Biodiversity responses to Lateglacial climate change in the subdecadally-resolved record of Lake Hämelsee (Germany) - S. Engels; C.S. Lane; W.Z. Hoek; I. Baneschi; A. Bouwman; E. Brogan; C. Bronk Ramsey; J. Collins; R. de Bruijn; A. Haliuc; O. Heiri; K. Hubay; et al. (Quaternary Science Reviews, 2024)

Lunar Flashlight science ground and flight measurements and operations using a multi-band laser reflectometer - Barbara A. Cohen; Ryan R. Petersburg; Daniel R. Cremons; Patrick S. Russell; Paul O. Hayne; Benjamin T. Greenhagen; David A. Paige; Jose Martinez Camacho; Nathan Cheek; Mark T. Sullivan; Valeria Lopez Robles; Jessica Ban; et al. (Icarus, 2024)

Fine-scale spatial and temporal trends in Red Sea coral reef research - Jesse E.M. Cochran; Alexander Kattan; Ute Langner; Anna M. Knochel; Susana Carvalho; Darren J. Coker; Lucy Fitzgerald; Kiana Ford; Micaela S.S. Justo; Royale S. Hardenstine; Ashlie J. McIvor; Viktor Nunes Peinemann; et al. (Regional Studies in Marine Science, 2024)

Clinical Investigation of Large Volume Subcutaneous Delivery up to 25 mL for Lean and Non-Lean Subjects - Xiangnan Dang; Han Shih; Rakesh Sharma; Daneen T. Angwin-Kaerner; Kathleen Lin; Shiven Kapur; Nagarajan R. Thyagarajapuram; Galen H. Shi; David S. Collins (Pharmaceutical Research, 2024)

Icequake insights on transient glacier slip mechanics near channelized subglacial drainage - Nathan T. Stevens; Lucas K. Zoet; Dougal D. Hansen; Richard B. Alley; Collin J. Roland; Emily Schwans; Cameron S. Shepherd (Earth and Planetary Science Letters, 2024)

Uncovering Ganymede's past: Tectonics at Nippur/Philus Sulci - Liliane M.L. Burkhard; Emily S. Costello; Bridget R. Smith-Konter; Marissa E. Cameron; Geoffrey C. Collins; Robert T. Pappalardo (Icarus, 2024)

Non-avian dinosaur eggshell calcite can contain ancient, endogenous amino acids - Evan T. Saitta; Jakob Vinther; Molly K. Crisp; Geoffrey D. Abbott; Lucy Wheeler; Samantha Presslee; Thomas G. Kaye; Ian Bull; Ian Fletcher; Xinqi Chen; Daniel Vidal; Fernando Sanguino; et al. (Geochimica et Cosmochimica Acta, 2024)

Collapse of Calcareous Silty Clay: Implication of Calcite Content and Wetting Fluid Type - Alfred Wilson Opukumo; Stephanie Glendinning; Collin T. Davie (Geotechnical and Geological Engineering, 2024)

Quantitative Structure Use Relationships: Highlights from a technical summit meeting - Rosemary T. Zaleski; Andreas Ahrens; Jon A. Arnot; Richard A. Becker; Mark Bonnell; Sean Collins; Paul DeLeo; Peter Egeghy; Michelle Embry; Todd Gouin; Kristin Isaacs; Elke Jensen (Regulatory Toxicology and Pharmacology, 2023)

Gill net catchability of walleye (Sander vitreus): Are provincial standards suitable for estimating adult density outside the region? - Adam G. Hansen; Michael W. Miller; Erik T. Cristan; Collin J. Farrell; Paul Winkle; Mandi M. Brandt; Kyle D. Battige; Jesse M. Lepak (Fisheries Research, 2023)

Red‐list status and extinction risk of the world's whales, dolphins, and porpoises - Gill T. Braulik; Barbara L. Taylor; Gianna Minton; Giuseppe Notarbartolo di Sciara; Tim Collins; Lorenzo Rojas‐Bracho; Enrique A. Crespo; Louisa S. Ponnampalam; Michael C. Double; Randall R. Reeves (Conservation Biology, 2023)
To understand the scope and scale of the loss of biodiversity, tools are required that can be applied in a standardized manner to all species globally, spanning realms from land to the open ocean. We used data from the International Union for the Conservation of Nature Red List to provide a synthesis of the conservation status and extinction risk of cetaceans. One in 4 cetacean species (26% of 92 species) was threatened with extinction (i.e., critically endangered, endangered, or vulnerable) and 11% were near threatened. Ten percent of cetacean species were data deficient, and we predicted that 2–3 of these species may also be threatened. The proportion of threatened cetaceans has increased: 15% in 1991, 19% in 2008, and 26% in 2021. The assessed conservation status of 20% of species has worsened from 2008 to 2021, and only 3 moved into categories of lesser threat. Cetacean species with small geographic ranges were more likely to be listed as threatened than those with large ranges, and those that occur in freshwater (100% of species) and coastal (60% of species) habitats were under the greatest threat. Analysis of odontocete species distributions revealed a global hotspot of threatened small cetaceans in Southeast Asia, in an area encompassing the Coral Triangle and extending through nearshore waters of the Bay of Bengal, northern Australia, and Papua New Guinea and into the coastal waters of China. Improved management of fisheries to limit overfishing and reduce bycatch is urgently needed to avoid extinctions or further declines, especially in coastal areas of Asia, Africa, and South America.

Mesoscale Shoreline Evolution on a Carbonate Sand Island: Anegada, British Virgin Islands - Anna Lisa Cescon; J. Andrew G. Cooper; Derek W. T. Jackson; Antoine Collin; Shannon Gore (Journal of Marine Science and Engineering, 2023)
Anegada, the easternmost island of the Virgin Islands group (Caribbean Sea), is a low Pleistocene carbonate platform surrounded by Horseshoe Reef, the world’s third-largest fringing reef. The western part of the island consists of an extensive beachridge plain (>40 ridges). The sandy carbonate shoreline exists in three morphodynamic domains that exhibit distinctive behaviour over the 59-year study period (1953 to 2012). The northern shore is dominated by westerly longshore drift under fair-weather conditions and cross-shore sediment transport during high-energy events. Storm wave run-up and high nearshore sediment availability contribute to the construction of shore-parallel beachridges. The western end of the island is affected by refracted waves that drive strong erosion and sediment transport. This is reflected in a succession of alternating rapid shoreline recession and progradation phases over the study period. The south–central shoreline is exposed to low wave energy and is stable and colonised by mangroves. The fringing reef plays a dominant role in mesoscale shoreline morphodynamics, both as a sediment source and in wave energy dissipation. Quasi-stable points and embayments suggest a strong influence of the reef framework in controlling the shoreline’s morphology and position. Sediment transfer from the reef to the shoreline appears to take place via shore-oblique, linear sediment transport pathways that develop across the lagoon in response to the modification of incoming waves. Cannibalisation of the shoreline sediment over the past 50 years is leading to straightening of the shoreline planform. This is counter to the long-term (Holocene) development of beachridges and suggests a change from a strongly positive to negative sediment budget.

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Soil nematode assemblages respond to interacting environmental changes - Laura Martinez; Shuqi Wu; Lauren Baur; Mariah T. Patton; Paul Owen-Smith; Scott L. Collins; Jennifer A. Rudgers (Oecologia, 2023)

Operationalizing crop model data assimilation for improved on-farm situational awareness - Matthew J. Knowling; Jeremy T. White; Dylan Grigg; Cassandra Collins; Seth Westra; Rob R. Walker; Anne Pellegrino; Bertram Ostendorf; Bree Bennett; Ayman Alzraiee (Agricultural and Forest Meteorology, 2023)

Balancing pre- and post-anthesis growth to maximise water-limited yield in cereals - Andrew K. Borrell; John T. Christopher; Alison Kelly; Brian Collins; Karine Chenu (Field Crops Research, 2023)

Comparing “apples” and “oranges” in the Woodford Shale: Pitfalls of the thermal maturity gradient approach for constraining evolution of mudrock porosity - Elizabeth T. Baruch; Stefan C. Löhr; Shujun Han; David N. Dewhurst; Alan S. Collins (Marine and Petroleum Geology, 2023)

Airborne levels of cadmium are correlated with urinary cadmium concentrations among young children living in the New York state city of Syracuse, USA - Dustin T. Hill; Vikrant Jandev; Michael Petroni; Nader Atallah-Yunes; Kestas Bendinskas; Lynn S. Brann; Kevin Heffernan; David A. Larsen; James A. MacKenzie; Christopher D. Palmer; Patrick J. Parsons; Brooks B. Gump; et al. (Environmental Research, 2023)

Hierarchical cue control of cocaine seeking in the face of cost - Val Collins; Kaisa N. Bornhoft; Amy Wolff; Sonal Sinha; Benjamin T. Saunders (Psychopharmacology, 2023)

Detection of SARS-CoV-2 RNA in wastewater and comparison to COVID-19 cases in two sewersheds, North Carolina, USA - Alyssa M. Grube; Collin K. Coleman; Connor D. LaMontagne; Megan E. Miller; Nikhil P. Kothegal; David A. Holcomb; A. Denene Blackwood; Thomas J. Clerkin; Marc L. Serre; Lawrence S. Engel; Virginia T. Guidry; Rachel T. Noble; et al. (Science of The Total Environment, 2023)

Long-term aircraft noise exposure and risk of hypertension in postmenopausal women - Daniel D. Nguyen; Eric A. Whitsel; Gregory A. Wellenius; Jonathan I. Levy; Jessica H. Leibler; Stephanie T. Grady; James D. Stewart; Matthew P. Fox; Jason M. Collins; Melissa N. Eliot; Andrew Malwitz; JoAnn E. Manson; et al. (Environmental Research, 2023)

Protein quality as a complementary functional unit in life cycle assessment (LCA) - G. A. McAuliffe; T. Takahashi; T. Beal; T. Huppertz; F. Leroy; J. Buttriss; A. L. Collins; A. Drewnowski; S. J. McLaren; F. Ortenzi; J. C. van der Pols; S. van Vliet; et al. (The International Journal of Life Cycle Assessment, 2023)
Goal and theoretical commentary A number of recent life cycle assessment (LCA) studies have concluded that animal-sourced foods should be restricted—or even avoided—within the human diet due to their relatively high environmental impacts (particularly those from ruminants) compared with other protein-rich foods (mainly protein-rich plant foods). From a nutritional point of view, however, issues such as broad nutrient bioavailability, amino acid balances, digestibility and even non-protein nutrient density (e.g., micronutrients) need to be accounted for before making such recommendations to the global population. This is especially important given the contribution of animal sourced foods to nutrient adequacy in the global South and vulnerable populations of high-income countries (e.g., children, women of reproductive age and elderly). Often, however, LCAs simplify this reality by using ‘protein’ as a functional unit in their models and basing their analyses on generic nutritional requirements. Even if a ‘nutritional functional unit’ (nFU) is utilised, it is unlikely to consider the complexities of amino acid composition and subsequent protein accretion. The discussion herein focuses on nutritional LCA (nLCA), particularly on the usefulness of nFUs such as ‘protein,’ and whether protein quality should be considered when adopting the nutrient as an (n)FU. Further, a novel and informative case study is provided to demonstrate the strengths and weaknesses of protein-quality adjustment. Case study methods To complement current discussions, we present an exploratory virtual experiment to determine how Digestible Indispensable Amino Acid Scores (DIAAS) might play a role in nLCA development by correcting for amino acid quality and digestibility. DIAAS is a scoring mechanism which considers the limiting indispensable amino acids (IAAs) within an IAA balance of a given food (or meal) and provides a percentage contribution relative to recommended daily intakes for IAA and subsequent protein anabolism; for clarity, we focus only on single food items (4 × animal-based products and 4 × plant-based products) in the current case exemplar. Further, we take beef as a sensitivity analysis example (which we particularly recommend when considering IAA complementarity at the meal-level) to elucidate how various cuts of the same intermediary product could affect the interpretation of nLCA results of the end-product(s). Recommendations First, we provide a list of suggestions which are intended to (a) assist with deciding whether protein-quality correction is necessary for a specific research question and (b) acknowledge additional uncertainties by providing mitigating opportunities to avoid misinterpretation (or worse, dis-interpretation) of protein-focused nLCA studies. We conclude that as relevant (primary) data availability from supply chain ‘gatekeepers’ (e.g., international agri-food distributors and processors) becomes more prevalent, detailed consideration of IAA provision of contrasting protein sources needs to be acknowledged—ideally quantitatively with DIAAS being one example—in nLCA studies utilising protein as a nFU. We also contend that future nLCA studies should discuss the complementarity of amino acid balances at the meal-level, as a minimum, rather than the product level when assessing protein metabolic responses of consumers. Additionally, a broader set of nutrients should ideally be included when evaluating “protein-rich foods” which provide nutrients that extend beyond amino acids, which is of particular importance when exploring dietary-level nLCA.

Stronger fertilization effects on aboveground versus belowground plant properties across nine U.S. grasslands - Adrienne B. Keller; Christopher A. Walter; Dana M. Blumenthal; Elizabeth T. Borer; Scott L. Collins; Lang C. DeLancey; Philip A. Fay; Kirsten S. Hofmockel; Johannes M. H. Knops; Andrew D. B. Leakey; Melanie A. Mayes; Eric W. Seabloom; et al. (Ecology, 2023)
Increased nutrient inputs due to anthropogenic activity are expected to increase primary productivity across terrestrial ecosystems, but changes in allocation aboveground versus belowground with nutrient addition have different implications for soil carbon (C) storage. Thus, given that roots are major contributors to soil C storage, understanding belowground net primary productivity (BNPP) and biomass responses to changes in nutrient availability is essential to predicting carbon–climate feedbacks in the context of interacting global environmental changes. To address this knowledge gap, we tested whether a decade of nitrogen (N) and phosphorus (P) fertilization consistently influenced aboveground and belowground biomass and productivity at nine grassland sites spanning a wide range of climatic and edaphic conditions in the continental United States. Fertilization effects were strong aboveground, with both N and P addition stimulating aboveground biomass at nearly all sites (by 30% and 36%, respectively, on average). P addition consistently increased root production (by 15% on average), whereas other belowground responses to fertilization were more variable, ranging from positive to negative across sites. Site‐specific responses to P were not predicted by the measured covariates. Atmospheric N deposition mediated the effect of N fertilization on root biomass and turnover. Specifically, atmospheric N deposition was positively correlated with root turnover rates, and this relationship was amplified with N addition. Nitrogen addition increased root biomass at sites with low N deposition but decreased it at sites with high N deposition. Overall, these results suggest that the effects of nutrient supply on belowground plant properties are context dependent, particularly with regard to background N supply rates, demonstrating that site conditions must be considered when predicting how grassland ecosystems will respond to increased nutrient loading from anthropogenic activity.

Assessing associations between residential proximity to greenspace and birth defects in the National Birth Defects Prevention Study - Kari A. Weber; Wei Yang; Suzan L. Carmichael; R. Thomas Collins; Thomas J. Luben; Tania A. Desrosiers; Tabassum Z. Insaf; Mimi T. Le; Shannon Pruitt Evans; Paul A. Romitti; Mahsa M. Yazdy; Wendy N. Nembhard; et al. (Environmental Research, 2023)

Targeted pollution management can significantly reduce toxic emissions while limiting adverse effects on employment in US manufacturing - Mary B. Collins; Simone Pulver; Dustin T. Hill; Ben Manski (Environmental Science & Policy, 2023)

Successful restoration of archived ovine formalin fixed paraffin-embedded tissue DNA and single nucleotide polymorphism analysis - Amanda Kravitz; Ron Tyler; B. Murali Manohar; B. Samuel Masilamoni Ronald; Michael T. Collins; Nammalwar Sriranganathan (Veterinary Research Communications, 2023)
Archived formalin fixed paraffin-embedded (FFPE) tissues are powerful tools in medicine, capable of harboring diagnostic and genetic answers to challenging clinical questions. Successful utilization of DNA derived from FFPE samples is dependent upon repairing DNA damage generated from the fixation process. Methods to repair FFPE DNA have been successful in human medicine for a variety of research and clinical applications, yet remain underutilized in veterinary medicine. Despite the available technology, our study is the first to evaluate the repair of FFPE derived DNA from veterinary species for single-nucleotide polymorphism (SNP) analysis using the Illumina OvineSNP50 BeadChip and Illumina FFPE QC and DNA Restore kit. To accomplish this, 48 ovine FFPE samples were run using the Illumina OvineSNP50 BeadChip with and without restoration. Compared to pre-restore data, we found increased sample call rates, SNP call frequency, and assay metrics for all samples post-restoration. Further, we utilized four sheep with available parallel fresh DNA and FFPE DNA to compare assay metrics and genotype calls between the two starting sample types. Although fresh samples generated increased call rates, we found 99% concordance in allele calls between restored FFPE and fresh DNA for all four samples. Our results indicate successful restoration and genotyping of ovine FFPE samples using this technology, with potential for utilization in other veterinary species.

Relative contributions of parasite consumptive and non-consumptive effects to host population suppression in simulated fly–mite populations - Collin J. Horn; Darcy R. Visscher; Lien T. Luong (Oecologia, 2022)

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Acanthopagrus oconnorae , a new species of seabream (Sparidae) from the Red Sea - Lucía Pombo‐Ayora; Viktor N. Peinemann; Collin T. Williams; Song He; Yu Jia Lin; Yukio Iwatsuki; Donal D. C. Bradley; Michael L. Berumen (Journal of Fish Biology, 2022)
A new species of sparid fish, Acanthopagrus oconnorae , is described based on 11 specimens collected in the shallow (0–1 m depth) mangrove‐adjacent sandflats of Thuwal, Saudi Arabia. The new species is distinguished from its congeners by the following combination of characters: second anal‐fin spine 12.8%–16.6% of standard length (SL); 3½ scale rows between the fifth dorsal‐fin spine and lateral line; suborbital width 5.7%–6.7% of SL; eyes positioned at the anterior edge of the head, often forming a weakly convex break in an otherwise gently curved head profile, when viewed laterally; caudal fin light yellow with black posterior margin (approximately half of fin); anal fin dusky grey, with posterior one‐fifth of the fin light yellow; black streaks on inter‐radial membranes of anal fin absent. The most similar species to A. oconnorae is Acanthopagrus vagus , which differs by the presence of a w‐shaped anterior edge of the scaled predorsal area, a more acute snout and black streaks on the inter‐radial membranes of the anal fin. Phylogenetic placement and species delimitation of A. oconnorae are discussed based on COI, CytB and 16S sequences. It is hypothesized that ecology and behaviour explain how this species avoided detection despite its likely occurrence in coastal areas of the Red Sea with historically high fishing pressure.

The carbon cost of the 2019–20 Australian fires varies with fire severity and forest type - Rachael H. Nolan; Luke Collins; Rebecca K. Gibson; Stephanie A. Samson; Katherine T. Rolls; Kirsty Milner; Belinda E. Medlyn; Owen F. Price; Anne Griebel; Brendan Choat; Mingkai Jiang; Matthias M. Boer (Global Ecology and Biogeography, 2022)
Aim To estimate loss of above‐ground carbon (AGC) and conversion of live carbon to dead carbon following understorey and canopy fire. Location South‐eastern Australia. Time period 2019–2020. Major taxa studied Four widespread resprouting eucalypt forests. Methods Above‐ground carbon was measured in 15 plots in each of four forest types one‐year post‐fire. We also assessed topkill, that is, trees subject to canopy loss that failed to resprout epicormically. Results While canopy fire was associated with greater declines in AGC than understorey fire, this was only statistically significant for only one forest type, where AGC declined from 154 to 85 Mg C ha −1 following canopy fire. Significant post‐fire increases in dead AGC were observed in one forest type, where dead carbon increased from 22 to 60% after canopy fire. Topkill of trees following canopy fire (48–78% of stems) was higher than topkill after understorey fire (36–53% of stems) and in unburnt forest (12–55%). Topkill occurred primarily in small‐diameter stems. Consequently, there was no effect of fire on the proportion of dead AGC in trees, with the exception of the forest with lowest productivity (i.e., lowest biomass) and lowest annual rainfall, where dead tree carbon increased from 8% in unburnt forest to 13 and 53% after understorey and canopy fire, respectively. AGC in understorey vegetation and coarse woody debris was similar or lower in burnt compared with unburnt forest. Litter carbon was significantly lower and pyrogenic carbon significantly higher in burnt forest, with no difference between understorey and canopy fire. Main conclusions While increased fire severity was associated with increased changes to carbon stocks, there were differences among forest types. Specifically, the driest forest type had the highest rates of topkill following canopy fire. These results highlight the importance of spatial variability in fire severity and forest type in determining the effects of fire on carbon stocks.

Assessing the quantity and toxicity of chemical releases from TRI facilities in Upstate New York - Amanda T. Charette; Dustin T. Hill; Mary B. Collins; Jaime E. Mirowsky (Journal of Environmental Studies and Sciences, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Two new triterpenoid fatty acid esters from Schefflera barteri Harms (Araliaceae) § - Judith Flore T. Mbougnia; Gabin Thierry M. Bitchagno; Steven Collins N. Wouamba; Jean-Bosco Jouda; Maurice Ducret Awouafack; Mathieu Tene; Bruno Ndjakou Lenta; Simeon Fogue Kouam; Pierre Tane; Norbert Sewald (Natural Product Research, 2022)

The Status of Marine Megafauna Research in Macaronesia: A Systematic Review - Ashlie J. McIvor; Collin T. Williams; Filipe Alves; Ana Dinis; Miguel P. Pais; João Canning-Clode (Frontiers in Marine Science, 2022)
Marine megafauna serve valuable ecological and economical roles globally, yet, many species have experienced precipitous population declines. The significance of marine megafauna is particularly evident in Macaronesia, a complex of oceanic archipelagos in the Northeast Atlantic Ocean. Macaronesian islands provide important habitats for marine megafauna species, in turn supporting considerable regional economic activity (e.g., ecotourism and fisheries). Despite this, concerted efforts to manage marine megafauna throughout Macaronesia have been limited. This systematic review provides the first description of the trends in marine megafauna research in this unique insular ecosystem, to provide a better understanding of taxa-specific research needs and future directions for conservation. We identified and validated 408 peer-reviewed publications until 2021 following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. Literature was dominated by marine mammal research conducted in the northern archipelagos (Azores, Madeira, and Canary Islands) and marine turtle research conducted in Cabo Verde. Much less research focused on large-bodied fish, especially in Madeira and Canary Islands, leaving some of the most vulnerable species regionally data deficient. Research across scientific disciplines focused more on biological studies than management and policy, and anthropogenic impacts were quantified more frequently on mammals or turtles and less on fishes. By identifying gaps in our knowledge of megafauna in relation to threats faced by these organisms, we offer taxa-specific recommendations for future research direction. Although, overall our results indicate that determining population level connectivity should be a major research priority among many marine megafauna species as this information is vital to numerous management strategies, including marine protected areas. In this review, we present a basis of understanding of the current work in Macaronesia, highlighting critical data gaps that are urgently needed to guide the next steps toward establishing conservation priorities for marine megafauna in the region.

Distinct colony boundaries and larval discrimination in polygyne red imported fire ants ( Solenopsis invicta ) - MacKenzie K. Kjeldgaard; Pierre‐André Eyer; Collin C. McMichael; Alison A. Bockoven; Joanie T. King; Ayumi Hyodo; Thomas W. Boutton; Edward L. Vargo; Micky D. Eubanks (Molecular Ecology, 2022)
Evaluating the factors that promote invasive ant abundance is critical to assess their ecological impact and inform their management. Many invasive ant species show reduced nestmate recognition and an absence of boundaries between unrelated nests, which allow populations to achieve greater densities due to reduced intraspecific competition. We examined nestmate discrimination and colony boundaries in introduced populations of the red imported fire ant ( Solenopsis invicta ; hereafter, fire ant). Fire ants occur in two social forms: monogyne (colonies with a single egg‐laying queen) and polygyne (colonies with multiple egg‐laying queens). In contrast with monogyne nests, polygyne nests are thought to be interconnected due to the reduced antagonism between non‐nestmate polygyne workers, perhaps because polygyne workers habituate the colony to an odour unique to Gp ‐ 9 b ‐carrying adults. However, colony boundaries and nestmate discrimination are poorly documented, particularly for worker‐brood interactions. To delimit boundaries between field colonies, we correlated the exchange of a 15 N‐glycine tracer dissolved in a sucrose solution with social form. We also evaluated nestmate discrimination between polygyne workers and larvae in the laboratory. Counter to our expectations, polygyne colonies behaved identically to monogyne colonies, suggesting both social forms maintain strict colony boundaries. Polygyne workers also preferentially fed larval nestmates and may have selectively cannibalized non‐nestmates. The levels of relatedness among workers in polygyne colonies was higher than those previously reported in North America (mean ± standard error: 0.269 ± 0.037). Our study highlights the importance of combining genetic analyses with direct quantification of resource exchange to better understand the factors influencing ant invasions.

Soil carbon stocks in temperate grasslands differ strongly across sites but are insensitive to decade‐long fertilization - Adrienne B. Keller; Elizabeth T. Borer; Scott L. Collins; Lang C. DeLancey; Philip A. Fay; Kirsten S. Hofmockel; Andrew D.B. Leakey; Melanie A. Mayes; Eric W. Seabloom; Christopher A. Walter; Yong Wang; Qian Zhao; et al. (Global Change Biology, 2022)
Enhancing soil carbon (C) storage has the potential to offset human‐caused increases in atmospheric CO 2 . Rising CO 2 has occurred concurrently with increasing supply rates of biologically limiting nutrients such as nitrogen (N) and phosphorus (P). However, it is unclear how increased supplies of N and P will alter soil C sequestration, particularly in grasslands, which make up nearly a third of non‐agricultural land worldwide. Here, we leverage a globally distributed nutrient addition experiment (the Nutrient Network) to examine how a decade of N and P fertilization (alone and in combination) influenced soil C and N stocks at nine grassland sites spanning the continental United States. We measured changes in bulk soil C and N stocks and in three soil C fractions (light and heavy particulate organic matter, and mineral‐associated organic matter fractions). Nutrient amendment had variable effects on soil C and N pools that ranged from strongly positive to strongly negative, while soil C and N pool sizes varied by more than an order of magnitude across sites. Piecewise SEM clarified that small increases in plant C inputs with fertilization did not translate to greater soil C storage. Nevertheless, peak season aboveground plant biomass (but not root biomass or production) was strongly positively related to soil C storage at seven of the nine sites, and across all nine sites, soil C covaried with moisture index and soil mineralogy, regardless of fertilization. Overall, we show that site factors such as moisture index, plant productivity, soil texture, and mineralogy were key predictors of cross‐site soil C, while nutrient amendment had weaker and site‐specific effects on C sequestration. This suggests that prioritizing the protection of highly productive temperate grasslands is critical for reducing future greenhouse gas losses arising from land use change.

Using an integrative research approach to improve fish migrations in regulated rivers: a case study on Pacific Salmon in the Seton River, Canada - Nolan N. Bett; Scott G. Hinch; Arthur L. Bass; Douglas C. Braun; Nicholas J. Burnett; Matthew T. Casselman; Steven J. Cooke; S. Matthew Drenner; Ahmed Gelchu; William L. Harrower; Roxx Ledoux; Andrew G. Lotto; et al. (Hydrobiologia, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Divergent responses of primary production to increasing precipitation variability in global drylands - Enqing Hou; Marcy E. Litvak; Jennifer A. Rudgers; Lifen Jiang; Scott L. Collins; William T. Pockman; Dafeng Hui; Shuli Niu; Yiqi Luo (Global Change Biology, 2021)
Interannual variability in precipitation has increased globally as climate warming intensifies. The increased variability impacts both terrestrial plant production and carbon (C) sequestration. However, mechanisms driving these changes are largely unknown. Here, we examined mechanisms underlying the response of aboveground net primary production (ANPP) to interannual precipitation variability in global drylands with mean annual precipitation (MAP) −1 , using a combined approach of data synthesis and process‐based modeling. We found a hump‐shaped response of ANPP to precipitation variability along the MAP gradient. The response was positive when MAP −1 and negative when MAP was higher than this threshold, with a positive peak at 140 mm year −1 . Transpiration and subsoil water content mirrored the response of ANPP to precipitation variability; evaporation responded negatively and water loss through runoff and drainage responded positively to precipitation variability. Mean annual temperature, soil type, and plant physiological traits all altered the magnitude but not the pattern of the response of ANPP to precipitation variability along the MAP gradient. By extrapolating to global drylands ( −1 MAP), we estimated that ANPP would increase by 15.2 ± 6.0 Tg C year −1 in arid and hyper‐arid lands and decrease by 2.1 ± 0.5 Tg C year −1 in dry sub‐humid lands under future changes in interannual precipitation variability. Thus, increases in precipitation variability will enhance primary production in many drylands in the future.

Coherence and cognition in the cortex: the fundamental role of parvalbumin, myelin, and the perineuronal net - Ellie A. Bucher; Jessica M. Collins; Anna E. King; James C. Vickers; Matthew T. K. Kirkcaldie (Brain Structure and Function, 2021)

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

Correction to: Neotype designation and re-description of Forsskål’s reticulate whipray Himantura uarnak - Philippe Borsa; Collin T. Williams; Ashlie J. McIvor; Thierry B. Hoareau; Michael L. Berumen (Marine Biodiversity, 2021)

Assessing residential socioeconomic factors associated with pollutant releases using EPA’s Toxic Release Inventory - Amanda T. Charette; Mary B. Collins; Jaime E. Mirowsky (Journal of Environmental Studies and Sciences, 2021)

Neotype designation and re-description of Forsskål’s reticulate whipray Himantura uarnak - Philippe Borsa; Collin T. Williams; Ashlie J. McIvor; Thierry B. Hoareau; Michael L. Berumen (Marine Biodiversity, 2021)

MDPV self-administration in female rats: influence of reinforcement history - Michelle R. Doyle; Agnieszka Sulima; Kenner C. Rice; Gregory T. Collins (Psychopharmacology, 2021)

Genetic diversity and life‐history traits of bonefish Albula spp. from the Red Sea - Collin T. Williams; Ashlie J. McIvor; Elizabeth M. Wallace; Yu‐Jia Lin; Michael L. Berumen (Journal of Fish Biology, 2021)
The management of bonefishes Albula spp. has been hindered by unresolved species distributions and a general lack of life‐history information. This study provides the first genetic species identifications of Albula spp. from the northern Indian Ocean. The roundjaw bonefish Albula glossodonta was documented in the Red Sea, and the smallscale bonefish A. oligolepis was identified in the Gulf of Aden with no evidence supporting sympatry. Estimates of genetic differentiation indicate three closely related lineages of A. glossodonta in the Red Sea, Indian Ocean and Pacific Ocean (Red Sea‐Pacific Ocean, F st = 0.295; Red Sea‐Seychelles, F st = 0.193; Pacific Ocean‐Seychelles, F st = 0.141). In addition, the authors provide the first life‐history information of Albula spp. in the Indian Ocean. Age‐based growth models of A. glossodonta from the Red Sea demonstrated statistically significant differences compared to previously published data from the Pacific Ocean. Spawning activity during winter months was derived from gonado‐somatic index values of A. glossodonta from the Red Sea and corresponded with spawning seasonality previously documented for the species in the Pacific Ocean. The results of this study aid in refining biogeographical uncertainties of Albula spp. and illustrate the importance of collecting regional growth information for subsequent management of A. glossodonta .

Increasing effects of chronic nutrient enrichment on plant diversity loss and ecosystem productivity over time - Eric W. Seabloom; Peter B. Adler; Juan Alberti; Lori Biederman; Yvonne M. Buckley; Marc W. Cadotte; Scott L. Collins; Laura Dee; Philip A. Fay; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; et al. (Ecology, 2021)
Human activities are enriching many of Earth’s ecosystems with biologically limiting mineral nutrients such as nitrogen (N) and phosphorus (P). In grasslands, this enrichment generally reduces plant diversity and increases productivity. The widely demonstrated positive effect of diversity on productivity suggests a potential negative feedback, whereby nutrient‐induced declines in diversity reduce the initial gains in productivity arising from nutrient enrichment. In addition, plant productivity and diversity can be inhibited by accumulations of dead biomass, which may be altered by nutrient enrichment. Over longer time frames, nutrient addition may increase soil fertility by increasing soil organic matter and nutrient pools. We examined the effects of 5–11 yr of nutrient addition at 47 grasslands in 12 countries. Nutrient enrichment increased aboveground live biomass and reduced plant diversity at nearly all sites, and these effects became stronger over time. We did not find evidence that nutrient‐induced losses of diversity reduced the positive effects of nutrients on biomass; however, nutrient effects on live biomass increased more slowly at sites where litter was also increasing, regardless of plant diversity. This work suggests that short‐term experiments may underestimate the long‐term nutrient enrichment effects on global grassland ecosystems.

Legacy Effects of Hydrologic Alteration in Playa Wetland Responses to Droughts - Micah T. Russell; Jennifer M. Cartwright; Gail H. Collins; Ryan A. Long; Jan H. Eitel (Wetlands, 2020)
Wetland conservation increasingly must account for climate change and legacies of previous land-use practices. Playa wetlands provide critical wildlife habitat, but may be impacted by intensifying droughts and previous hydrologic modifications. To inform playa restoration planning, we asked: (1) what are the trends in playa inundation? (2) what are the factors influencing inundation? (3) how is playa inundation affected by increasingly severe drought? (4) do certain playas provide hydrologic refugia during droughts, and (5) if so, how are refugia patterns related to historical modifications? Using remotely sensed surface-water data, we evaluated a 30-year time series (1985–2015) of inundation for 153 playas of the Great Basin, USA. Inundation likelihood and duration increased with wetter weather conditions and were greater in modified playas. Inundation probability was projected to decrease from 22% under average conditions to 11% under extreme drought, with respective annual inundation decreasing from 1.7 to 0.9 months. Only 4% of playas were inundated for at least 2 months in each of the 5 driest years, suggesting their potential as drought refugia. Refugial playas were larger and more likely to have been modified, possibly because previous land managers selected refugial playas for modification. These inundation patterns can inform efforts to restore wetland functions and to conserve playa habitats as climate conditions change.

Forest Vegetation Change and Its Impacts on Soil Water Following 47 Years of Managed Wildfire - Jens T. Stevens; Gabrielle F. S. Boisramé; Ekaterina Rakhmatulina; Sally E. Thompson; Brandon M. Collins; Scott L. Stephens (Ecosystems, 2020)

Above and below: Military Aircraft Noise in Air and under Water at Whidbey Island, Washington - Lauren M. Kuehne; Christine Erbe; Erin Ashe; Laura T. Bogaard; Marena Salerno Collins; Rob Williams (Journal of Marine Science and Engineering, 2020)
Military operations may result in noise impacts on surrounding communities and wildlife. A recent transition to more powerful military aircraft and a national consolidation of training operations to Whidbey Island, WA, USA, provided a unique opportunity to measure and assess both in-air and underwater noise associated with military aircraft. In-air noise levels (110 ± 4 dB re 20 µPa rms and 107 ± 5 dBA) exceeded known thresholds of behavioral and physiological impacts for humans, as well as terrestrial birds and mammals. Importantly, we demonstrate that the number and cumulative duration of daily overflights exceed those in a majority of studies that have evaluated impacts of noise from military aircraft worldwide. Using a hydrophone deployed near one runway, we also detected sound signatures of aircraft at a depth of 30 m below the sea surface, with noise levels (134 ± 3 dB re 1 µPa rms) exceeding thresholds known to trigger behavioral changes in fish, seabirds, and marine mammals, including Endangered Southern Resident killer whales. Our study highlights challenges and problems in evaluating the implications of increased noise pollution from military operations, and knowledge gaps that should be prioritized with respect to understanding impacts on people and sensitive wildlife.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Evaluation of repeated or acute treatment with cannabidiol (CBD), cannabidiolic acid (CBDA) or CBDA methyl ester (HU-580) on nausea and/or vomiting in rats and shrews - Erin M. Rock; Megan T. Sullivan; Stephen A. Collins; Hannah Goodman; Cheryl L. Limebeer; Raphael Mechoulam; Linda A. Parker (Psychopharmacology, 2020)

Public money and private interests: United States government contract awardees’ contribution to industrial pollution production - Dustin T. Hill; Elizabeth S. Vidon; Mary B. Collins (Journal of Environmental Studies and Sciences, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Microbial processing of plant remains is co‐limited by multiple nutrients in global grasslands - Raúl Ochoa‐Hueso; Elizabeth T. Borer; Eric W. Seabloom; Sarah E. Hobbie; Anita C. Risch; Scott L. Collins; Juan Alberti; Héctor A. Bahamonde; Cynthia S. Brown; Maria C. Caldeira; Pedro Daleo; Chris R. Dickman; et al. (Global Change Biology, 2020)
Microbial processing of aggregate‐unprotected organic matter inputs is key for soil fertility, long‐term ecosystem carbon and nutrient sequestration and sustainable agriculture. We investigated the effects of adding multiple nutrients (nitrogen, phosphorus and potassium plus nine essential macro‐ and micro‐nutrients) on decomposition and biochemical transformation of standard plant materials buried in 21 grasslands from four continents. Addition of multiple nutrients weakly but consistently increased decomposition and biochemical transformation of plant remains during the peak‐season, concurrent with changes in microbial exoenzymatic activity. Higher mean annual precipitation and lower mean annual temperature were the main climatic drivers of higher decomposition rates, while biochemical transformation of plant remains was negatively related to temperature of the wettest quarter. Nutrients enhanced decomposition most at cool, high rainfall sites, indicating that in a warmer and drier future fertilized grassland soils will have an even more limited potential for microbial processing of plant remains.

Quality–quantity trade‐offs drive functional trait evolution in a model microalgal ‘climate change winner’ - Rasmus T. Lindberg; Sinéad Collins (Ecology Letters, 2020)
Phytoplankton are the unicellular photosynthetic microbes that form the base of aquatic ecosystems, and their responses to global change will impact everything from food web dynamics to global nutrient cycles. Some taxa respond to environmental change by increasing population growth rates in the short‐term and are projected to increase in frequency over decades. To gain insight into how these projected ‘climate change winners’ evolve, we grew populations of microalgae in ameliorated environments for several hundred generations. Most populations evolved to allocate a smaller proportion of carbon to growth while increasing their ability to tolerate and metabolise reactive oxygen species (ROS). This trade‐off drives the evolution of traits that underlie the ecological and biogeochemical roles of phytoplankton. This offers evolutionary and a metabolic frameworks for understanding trait evolution in projected ‘climate change winners’ and suggests that short‐term population booms have the potential to be dampened or reversed when environmental amelioration persists.

Quantifying Topographic Characteristics of Wetlandscapes - Collin Branton; Derek T. Robinson (Wetlands, 2020)

Correction to: Quantifying Topographic Characteristics of Wetlandscapes - Collin Branton; Derek T. Robinson (Wetlands, 2020)

The response of stomatal conductance to seasonal drought in tropical forests - Jin Wu; Shawn P. Serbin; Kim S. Ely; Brett T. Wolfe; L. Turin Dickman; Charlotte Grossiord; Sean T. Michaletz; Adam D. Collins; Matteo Detto; Nate G. McDowell; S. Joseph Wright; Alistair Rogers (Global Change Biology, 2020)
Stomata regulate CO 2 uptake for photosynthesis and water loss through transpiration. The approaches used to represent stomatal conductance ( g s ) in models vary. In particular, current understanding of drivers of the variation in a key parameter in those models, the slope parameter (i.e. a measure of intrinsic plant water‐use‐efficiency), is still limited, particularly in the tropics. Here we collected diurnal measurements of leaf gas exchange and leaf water potential (Ψ leaf ), and a suite of plant traits from the upper canopy of 15 tropical trees in two contrasting Panamanian forests throughout the dry season of the 2016 El Niño. The plant traits included wood density, leaf‐mass‐per‐area (LMA), leaf carboxylation capacity ( V c,max ), leaf water content, the degree of isohydry, and predawn Ψ leaf . We first investigated how the choice of four commonly used leaf‐level g s models with and without the inclusion of Ψ leaf as an additional predictor variable influence the ability to predict g s , and then explored the abiotic (i.e. month, site‐month interaction) and biotic (i.e. tree‐species‐specific characteristics) drivers of slope parameter variation. Our results show that the inclusion of Ψ leaf did not improve model performance and that the models that represent the response of g s to vapor pressure deficit performed better than corresponding models that respond to relative humidity. Within each g s model, we found large variation in the slope parameter, and this variation was attributable to the biotic driver, rather than abiotic drivers. We further investigated potential relationships between the slope parameter and the six available plant traits mentioned above, and found that only one trait, LMA, had a significant correlation with the slope parameter ( R 2 = 0.66, n = 15), highlighting a potential path towards improved model parameterization. This study advances understanding of g s dynamics over seasonal drought, and identifies a practical, trait‐based approach to improve modeling of carbon and water exchange in tropical forests.

Arbuscular mycorrhizal fungi in roots and soil respond differently to biotic and abiotic factors in the Serengeti - Bo Maxwell Stevens; Jeffrey Ryan Propster; Maarja Öpik; Gail W. T. Wilson; Sara Lynne Alloway; Emilian Mayemba; Nancy Collins Johnson (Mycorrhiza, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Self-administration of the synthetic cathinones 3,4-methylenedioxypyrovalerone (MDPV) and α-pyrrolidinopentiophenone (α-PVP) in rhesus monkeys - Gregory T. Collins; Agnieszka Sulima; Kenner C. Rice; Charles P. France (Psychopharmacology, 2019)

The case for emulating insect brains using anatomical “wiring diagrams” equipped with biophysical models of neuronal activity - Logan T. Collins (Biological Cybernetics, 2019)

Using Cumulative Impact Mapping to Prioritize Marine Conservation Efforts in Equatorial Guinea - Brittany T. Trew; Hedley S. Grantham; Christian Barrientos; Tim Collins; Philip D. Doherty; Angela Formia; Brendan J. Godley; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Dominic Tilley; Matthew J. Witt; et al. (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Current parasite resistance trades off with future defenses and flight performance - Collin J. Horn; Lien T. Luong (Behavioral Ecology and Sociobiology, 2019)

Experimental drought reduces genetic diversity in the grassland foundation species Bouteloua eriopoda - Kenneth D. Whitney; Joann Mudge; Donald O. Natvig; Anitha Sundararajan; William T. Pockman; Jennifer Bell; Scott L. Collins; Jennifer A. Rudgers (Oecologia, 2019)

Behavioral economic analysis of the reinforcing effects of “bath salts” mixtures: studies with MDPV, methylone, and caffeine in male Sprague-Dawley rats - Brenda M. Gannon; Melson P. Mesmin; Agnieszka Sulima; Kenner C. Rice; Gregory T. Collins (Psychopharmacology, 2019)

Botryosphaeriales associated with stem blight and dieback of blueberry (Vaccinium spp.) in New South Wales and Western Australia - Kelly A. Scarlett; Lucas A. Shuttleworth; Damian Collins; Chris T. Rothwell; David I. Guest; Rosalie Daniel (Australasian Plant Pathology, 2019)

Selective Enzymatic Digestion of Proteoglycans and Collagens Alters Cartilage T1rho and T2 Relaxation Times - Amber T. Collins; Courtney C. Hatcher; Sophia Y. Kim; Sophia N. Ziemian; Charles E. Spritzer; Farshid Guilak; Louis E. DeFrate; Amy L. McNulty (Annals of Biomedical Engineering, 2019)

Acquisition of obligate mutualist symbionts during the larval stage is not beneficial for a coral host - Aaron C. Hartmann; Kristen L. Marhaver; Anke Klueter; Michael T. Lovci; Collin J. Closek; Erika Diaz; Valérie F. Chamberland; Frederick I. Archer; Dimitri D. Deheyn; Mark J. A. Vermeij; Mónica Medina (Molecular Ecology, 2019)
Theory suggests that the direct transmission of beneficial endosymbionts (mutualists) from parents to offspring (vertical transmission) in animal hosts is advantageous and evolutionarily stable, yet many host species instead acquire their symbionts from the environment (horizontal acquisition). An outstanding question in marine biology is why some scleractinian corals do not provision their eggs and larvae with the endosymbiotic dinoflagellates that are necessary for a juvenile's ultimate survival. We tested whether the acquisition of photosynthetic endosymbionts (family Symbiodiniaceae) during the planktonic larval stage was advantageous, as is widely assumed, in the ecologically important and threatened Caribbean reef‐building coral Orbicella faveolata . Following larval acquisition, similar changes occurred in host energetic lipid use and gene expression regardless of whether their symbionts were photosynthesizing, suggesting the symbionts did not provide the energetic benefit characteristic of the mutualism in adults. Larvae that acquired photosymbionts isolated from conspecific adults on their natal reef exhibited a reduction in swimming, which may interfere with their ability to find suitable settlement substrate, and also a decrease in survival. Larvae exposed to two cultured algal species did not exhibit differences in survival, but decreased their swimming activity in response to one species. We conclude that acquiring photosymbionts during the larval stage confers no advantages and can in fact be disadvantageous to this coral host. The timing of symbiont acquisition appears to be a critical component of a host's life history strategy and overall reproductive fitness, and this timing itself appears to be under selective pressure.

Staqeya: the lone wolf at the edge of its ecological niche - Dylan Collins; Cheryl Alexander; Chris T. Darimont (Ecology, 2019)

Shark depredation in commercial and recreational fisheries - J. D. Mitchell; D. L. McLean; S. P. Collin; T. J. Langlois (Reviews in Fish Biology and Fisheries, 2018)

Whole‐river manipulation of olfactory cues affects upstream migration of sockeye salmon - S. Matthew Drenner; William L. Harrower; Matt T. Casselman; Nolan N. Bett; Aurthor L. Bass; Collin T. Middleton; Scott G. Hinch (Fisheries Management and Ecology, 2018)
This study experimentally manipulated olfactory cues in a river by adjusting hydropower operation and monitored behavioural responses of 193 adult sockeye salmon, Oncorhynchus nerka (Walbaum), using radio telemetry. Experimental dilution of olfactory cues in a tributary to 72% natal water relative to non‐natal water was associated with 80% reduced odds of fish entering the tributary from a river mainstem and increased migration times by an average of 12.2 hr, with females taking 4.6 hr longer than males to enter the tributary. Additionally, males delayed 2.7 hr longer than females at a diversion outlet in the river mainstem that discharged a natal water source during experimentally diluted olfactory conditions. Increased migration time associated with dilute olfactory cues would decrease energy available for reproduction and potentially reduce fitness. Hydropower managers should continue to regulate natal water conditions in the Seton River during sockeye salmon migrations to avoid negative impacts on migration timing and success.

Provenance and structure of the Yancannia Formation, southern Thomson Orogen: implications for the tectono-stratigraphic evolution of the Cambro-Ordovician western Tasmanides - S. C. T. Wong; W. J. Collins; A. C. Hack; H.-Q. Huang (Australian Journal of Earth Sciences, 2018)

Spatial heterogeneity in species composition constrains plant community responses to herbivory and fertilisation - Dorothee Hodapp; Elizabeth T. Borer; W. Stanley Harpole; Eric M. Lind; Eric W. Seabloom; Peter B. Adler; Juan Alberti; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Marc Cadotte; Elsa E. Cleland; et al. (Ecology Letters, 2018)
Environmental change can result in substantial shifts in community composition. The associated immigration and extinction events are likely constrained by the spatial distribution of species. Still, studies on environmental change typically quantify biotic responses at single spatial (time series within a single plot) or temporal (spatial beta diversity at single time points) scales, ignoring their potential interdependence. Here, we use data from a global network of grassland experiments to determine how turnover responses to two major forms of environmental change – fertilisation and herbivore loss – are affected by species pool size and spatial compositional heterogeneity. Fertilisation led to higher rates of local extinction, whereas turnover in herbivore exclusion plots was driven by species replacement. Overall, sites with more spatially heterogeneous composition showed significantly higher rates of annual turnover, independent of species pool size and treatment. Taking into account spatial biodiversity aspects will therefore improve our understanding of consequences of global and anthropogenic change on community dynamics.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Investigation of co‐infections with pathogens associated with gill disease in Atlantic salmon during an amoebic gill disease outbreak - J K Downes; T Yatabe; M Marcos‐Lopez; H D Rodger; E MacCarthy; I O'Connor; E Collins; N M Ruane (Journal of Fish Diseases, 2018)
Gill diseases are a complex and multifactorial challenge for marine farmed Atlantic salmon. Co‐infections with putative pathogens are common on farms; however, there is a lack of knowledge in relation to the potential effect co‐infections may have on pathology. The objective of this study was to determine the prevalence and potential effects of Neoparamoeba perurans, Desmozoon lepeophtherii , Candidatus Branchiomonas cysticola, Tenacibaculum maritimum and salmon gill poxvirus ( SGPV ) during a longitudinal study on a marine Atlantic salmon farm. Real‐time PCR was used to determine the presence and sequential infection patterns of these pathogens on gill samples collected from stocking until harvest. A number of multilevel models were used to determine the effect of these putative pathogens on gill health (measured as gill histopathology score), while adjusting for the effect of water temperature and time since the last freshwater treatment. Results indicate that between 12 and 16 weeks post‐seawater transfer (wpst), colonization of the gills by all pathogens had commenced and by week 16 of marine production each of the pathogens had been detected. D. lepeophtherii and Candidatus B. cysticola were by far the most prevalent of the potential pathogens detected during this study. Detections of T. maritimum were found to be significantly correlated with temperature showing distinct seasonality. Salmon gill poxvirus was found to be highly sporadic and detected in the first sampling point, suggesting a carryover from the freshwater stage of production. Finally, the model results indicated no clear effect between any of the pathogens. Additionally, the models showed that the only variable which had a consistent effect on the histology score was N. perurans .

Drought consistently alters the composition of soil fungal and bacterial communities in grasslands from two continents - Raúl Ochoa‐Hueso; Scott L. Collins; Manuel Delgado‐Baquerizo; Kelly Hamonts; William T. Pockman; Robert L. Sinsabaugh; Melinda D. Smith; Alan K. Knapp; Sally A. Power (Global Change Biology, 2018)
The effects of short‐term drought on soil microbial communities remain largely unexplored, particularly at large scales and under field conditions. We used seven experimental sites from two continents (North America and Australia) to evaluate the impacts of imposed extreme drought on the abundance, community composition, richness, and function of soil bacterial and fungal communities. The sites encompassed different grassland ecosystems spanning a wide range of climatic and soil properties. Drought significantly altered the community composition of soil bacteria and, to a lesser extent, fungi in grasslands from two continents. The magnitude of the fungal community change was directly proportional to the precipitation gradient. This greater fungal sensitivity to drought at more mesic sites contrasts with the generally observed pattern of greater drought sensitivity of plant communities in more arid grasslands, suggesting that plant and microbial communities may respond differently along precipitation gradients. Actinobateria, and Chloroflexi, bacterial phyla typically dominant in dry environments, increased their relative abundance in response to drought, whereas Glomeromycetes, a fungal class regarded as widely symbiotic, decreased in relative abundance. The response of Chlamydiae and Tenericutes, two phyla of mostly pathogenic species, decreased and increased along the precipitation gradient, respectively. Soil enzyme activity consistently increased under drought, a response that was attributed to drought‐induced changes in microbial community structure rather than to changes in abundance and diversity. Our results provide evidence that drought has a widespread effect on the assembly of microbial communities, one of the major drivers of soil function in terrestrial ecosystems. Such responses may have important implications for the provision of key ecosystem services, including nutrient cycling, and may result in the weakening of plant–microbial interactions and a greater incidence of certain soil‐borne diseases.

A tutorial on model informed approaches to cardiovascular safety with focus on cardiac repolarisation - S. Y. A. Cheung; J. Parkinson; U. Wählby-Hamrén; C. D. Dota; Å. M. Kragh; L. Bergenholm; T. Vik; T. Collins; C. Arfvidsson; C. E. Pollard; H. K. Tomkinson; B. Hamrén (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Improving reliability of species identification and logbook catch reporting by commercial fishers in an Australian demersal shark longline fishery - W. G. Macbeth; P. A. Butcher; D. Collins; S. P. McGrath; S. C. Provost; A. C. Bowling; P. T. Geraghty; V. M. Peddemors (Fisheries Management and Ecology, 2018)
Large adult carcharhinid and sphyrnid sharks have been targeted in coastal waters off New South Wales, eastern Australia, by commercial fishers using demersal longlines since 2005. Inaccurate fisher reporting of the composition of catches led in 2008 to a range of complementary management measures to help improve reliability, including a redesigned catch logbook, species identification guide and at‐sea education via an observer programme. This study provides results from assessments of the effectiveness of those measures. A questionnaire yielded overwhelmingly positive feedback from fishers regarding the usefulness of the species identification guide. Comparison of observer‐recorded data and corresponding fisher‐reported logbook data via weighted linear mixed‐effects modelling found that since 2008, misreporting of catches has varied considerably among species and, for some species, among fishers. With some species commonly under‐reported and others frequently over‐reported, it is apparent that certain species were likely mistaken for other morphologically similar species. Such systematic error inherently undermines stock assessments of these vulnerable species. Management strategies designed to include education and extension will ensure greater reliability of fisher reporting of shark catches in the future.

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Asymmetric responses of primary productivity to precipitation extremes: A synthesis of grassland precipitation manipulation experiments - Kevin R. Wilcox; Zheng Shi; Laureano A. Gherardi; Nathan P. Lemoine; Sally E. Koerner; David L. Hoover; Edward Bork; Kerry M. Byrne; James Cahill; Scott L. Collins; Sarah Evans; Anna K. Gilgen; et al. (Global Change Biology, 2017)
Climatic changes are altering Earth's hydrological cycle, resulting in altered precipitation amounts, increased interannual variability of precipitation, and more frequent extreme precipitation events. These trends will likely continue into the future, having substantial impacts on net primary productivity ( NPP ) and associated ecosystem services such as food production and carbon sequestration. Frequently, experimental manipulations of precipitation have linked altered precipitation regimes to changes in NPP . Yet, findings have been diverse and substantial uncertainty still surrounds generalities describing patterns of ecosystem sensitivity to altered precipitation. Additionally, we do not know whether previously observed correlations between NPP and precipitation remain accurate when precipitation changes become extreme. We synthesized results from 83 case studies of experimental precipitation manipulations in grasslands worldwide. We used meta‐analytical techniques to search for generalities and asymmetries of aboveground NPP ( ANPP ) and belowground NPP ( BNPP ) responses to both the direction and magnitude of precipitation change. Sensitivity (i.e., productivity response standardized by the amount of precipitation change) of BNPP was similar under precipitation additions and reductions, but ANPP was more sensitive to precipitation additions than reductions; this was especially evident in drier ecosystems. Additionally, overall relationships between the magnitude of productivity responses and the magnitude of precipitation change were saturating in form. The saturating form of this relationship was likely driven by ANPP responses to very extreme precipitation increases, although there were limited studies imposing extreme precipitation change, and there was considerable variation among experiments. This highlights the importance of incorporating gradients of manipulations, ranging from extreme drought to extreme precipitation increases into future climate change experiments. Additionally, policy and land management decisions related to global change scenarios should consider how ANPP and BNPP responses may differ, and that ecosystem responses to extreme events might not be predicted from relationships found under moderate environmental changes.

Estimation of 3D Ground Reaction Force Using Nanocomposite Piezo-Responsive Foam Sensors During Walking - Parker G. Rosquist; Gavin Collins; A. Jake Merrell; Noelle J. Tuttle; James B. Tracy; Evan T. Bird; Matthew K. Seeley; David T. Fullwood; William F. Christensen; Anton E. Bowden (Annals of Biomedical Engineering, 2017)

Thermoregulation of the bovine scrotum 1: measurements of free-range animals in a paddock and pen - Andrea L. Wallage; S. D. Johnston; A. T. Lisle; L. Beard; A. M. Lees; C. W. Collins; J. B. Gaughan (International Journal of Biometeorology, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Measurement of bovine body and scrotal temperature using implanted temperature sensitive radio transmitters, data loggers and infrared thermography - A. L. Wallage; J. B. Gaughan; A. T. Lisle; L. Beard; C. W. Collins; S. D. Johnston (International Journal of Biometeorology, 2017)

Detection of a novel gammaherpesvirus (genus Rhadinovirus) in wild muntjac deer in Northern Ireland - John McKillen; Kayleigh Hogg; Paula Lagan; Cheryl Ball; Simon Doherty; Neil Reid; Lisa Collins; Jaimie T. A. Dick (Archives of Virology, 2017)

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Developmental pathways in lung regeneration - Collin T. Stabler; Edward E. Morrisey (Cell and Tissue Research, 2017)

Independent evolution of sexual dimorphism and female‐limited mimicry in swallowtail butterflies ( Papilio dardanus and Papilio phorcas ) - M. J. T. N. Timmermans; M. J. Thompson; S. Collins; A. P. Vogler (Molecular Ecology, 2017)
Several species of swallowtail butterflies (genus Papilio ) are Batesian mimics that express multiple mimetic female forms, while the males are monomorphic and nonmimetic. The evolution of such sex‐limited mimicry may involve sexual dimorphism arising first and mimicry subsequently. Such a stepwise scenario through a nonmimetic, sexually dimorphic stage has been proposed for two closely related sexually dimorphic species: Papilio phorcas, a nonmimetic species with two female forms, and Papilio dardanus , a female‐limited polymorphic mimetic species. Their close relationship indicates that female‐limited polymorphism could be a shared derived character of the two species. Here, we present a phylogenomic analysis of the dardanus group using 3964 nuclear loci and whole mitochondrial genomes, showing that they are not sister species and thus that the sexually dimorphic state has arisen independently in the two species. Nonhomology of the female polymorphism in both species is supported by population genetic analysis of engrailed , the presumed mimicry switch locus in P. dardanus . McDonald–Kreitman tests performed on SNP s in engrailed showed the signature of balancing selection in a polymorphic population of P. dardanus , but not in monomorphic populations , nor in the nonmimetic P. phorcas . Hence, the wing polymorphism does not balance polymorphisms in engrailed in P. phorcas . Equally, unlike in P. dardanus , none of the SNP s in P. phorcas engrailed were associated with either female morph. We conclude that sexual dimorphism due to female polymorphism evolved independently in both species from monomorphic, nonmimetic states. While sexual selection may drive male–female dimorphism in nonmimetic species, in mimetic Papilios, natural selection for protection from predators in females is an alternative route to sexual dimorphism.

Press–pulse interactions: effects of warming, N deposition, altered winter precipitation, and fire on desert grassland community structure and dynamics - Scott L. Collins; Laura M. Ladwig; Matthew D. Petrie; Sydney K. Jones; John M. Mulhouse; James R. Thibault; William T. Pockman (Global Change Biology, 2017)
Global environmental change is altering temperature, precipitation patterns, resource availability, and disturbance regimes. Theory predicts that ecological presses will interact with pulse events to alter ecosystem structure and function. In 2006, we established a long‐term, multifactor global change experiment to determine the interactive effects of nighttime warming, increased atmospheric nitrogen (N) deposition, and increased winter precipitation on plant community structure and aboveground net primary production ( ANPP ) in a northern Chihuahuan Desert grassland. In 2009, a lightning‐caused wildfire burned through the experiment. Here, we report on the interactive effects of these global change drivers on pre‐ and postfire grassland community structure and ANPP . Our nighttime warming treatment increased winter nighttime air temperatures by an average of 1.1 °C and summer nighttime air temperature by 1.5 °C. Soil N availability was 2.5 times higher in fertilized compared with control plots. Average soil volumetric water content ( VWC ) in winter was slightly but significantly higher (13.0% vs. 11.0%) in plots receiving added winter rain relative to controls, and VWC was slightly higher in warmed (14.5%) compared with control (13.5%) plots during the growing season even though surface soil temperatures were significantly higher in warmed plots. Despite these significant treatment effects, ANPP and plant community structure were highly resistant to these global change drivers prior to the fire. Burning reduced the cover of the dominant grasses by more than 75%. Following the fire, forb species richness and biomass increased significantly, particularly in warmed, fertilized plots that received additional winter precipitation. Thus, although unburned grassland showed little initial response to multiple ecological presses, our results demonstrate how a single pulse disturbance can interact with chronic alterations in resource availability to increase ecosystem sensitivity to multiple drivers of global environmental change.

Spatial distribution of aquatic marine fungi across the western Arctic and sub‐arctic - Brandon T. Hassett; Anne‐Lise L Ducluzeau; Roy E. Collins; Rolf Gradinger (Environmental Microbiology, 2017)
Summary Fungi are important parasites of primary producers and nutrient cyclers in aquatic ecosystems. In the Pacific‐Arctic domain, fungal parasitism is linked to light intensities and algal stress that can elevate disease incidence on algae and reduce diatom concentrations. Fungi are vastly understudied in the marine realm and knowledge of their function is constrained by the current understanding of fungal distribution and drivers on global scales. To investigate the spatial distribution of fungi in the western Arctic and sub‐Arctic, we used high throughput methods to sequence 18S rRNA, cloned and sequenced 28S rRNA and microscopically counted chytrid‐infected diatoms. We identified a broad distribution of fungal taxa predominated by Chytridiomycota and Dikarya. Phylogenetic analysis of our Chytridiomycota clones placed Arctic marine fungi sister to the order Lobulomycetales. This clade of fungi predominated in fungal communities under ice with low snowpack. Microscopic examination of fixed seawater and sea ice samples revealed chytrids parasitizing diatoms collected across the Arctic that notably infected 25% of a single diatom species in the Bering Sea. The Pezizomycotina comprised > 95% of eukaryotic sequence reads in Greenland, providing preliminary evidence for osmotrophs being a substitute for algae as the base of food webs.

Early Disruption of Extracellular Pleiotrophin Distribution Alters Cerebellar Neuronal Circuit Development and Function - M. M. Hamza; S. A. Rey; P. Hilber; A. Arabo; T. Collin; D. Vaudry; D. Burel (Molecular Neurobiology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

A comparative approach to assess drivers of success in mammalian conservation recovery programs - Jennifer J. Crees; Amy C. Collins; P. J. Stephenson; Helen M. R. Meredith; Richard P. Young; Caroline Howe; Mark R. Stanley Price; Samuel T. Turvey (Conservation Biology, 2016)
The outcomes of species recovery programs have been mixed; high‐profile population recoveries contrast with species‐level extinctions. Each conservation intervention has its own challenges, but to inform more effective management it is imperative to assess whether correlates of wider recovery program success or failure can be identified. To contribute to evidence‐based improvement of future conservation strategies, we conducted a global quantitative analysis of 48 mammalian recovery programs. We reviewed available scientific literature and conducted semistructured interviews with conservation professionals involved in different recovery programs to investigate ecological, management, and political factors associated with population recoveries or declines. Identifying and removing threats was significantly associated with increasing population trend and decreasing conservation dependence, emphasizing that populations are likely to continue to be compromised in the absence of effective threat mitigation and supporting the need for threat monitoring and adaptive management in response to new and potential threats. Lack of habitat and small population size were cited as limiting factors in 56% and 42% of recovery programs, respectively, and both were statistically associated with increased longer term dependence on conservation intervention, demonstrating the importance of increasing population numbers quickly and restoring and protecting habitat. Poor stakeholder coordination and management were also regularly cited by respondents as key weaknesses in recovery programs, indicating the importance of effective leadership and shared goals and management plans. Project outcomes were not influenced by biological or ecological variables such as body mass or habitat, which suggests that these insights into correlates of conservation success and failure are likely to be generalizable across mammals.

It’s what’s inside that counts: egg contaminant concentrations are influenced by estimates of egg density, egg volume, and fresh egg mass - Mark P. Herzog; Joshua T. Ackerman; Collin A. Eagles-Smith; C. Alex Hartman (Ecotoxicology, 2016)

Serum concentrations of chlorinated dibenzo-p-dioxins, furans and PCBs, among former phenoxy herbicide production workers and firefighters in New Zealand - Andrea ‘t Mannetje; Amanda Eng; Chris Walls; Evan Dryson; Dave McLean; Manolis Kogevinas; Jeff Fowles; Barry Borman; Patrick O’Connor; Soo Cheng; Collin Brooks; Allan H. Smith; et al. (International Archives of Occupational and Environmental Health, 2016)

An eDNA assay for Irish Petromyzon marinus and Salmo trutta and field validation in running water - M. S. Gustavson; P. C. Collins; J. A. Finarelli; D. Egan; R. Ó. Conchúir; G. D. Wightman; J. J. King; D. T. Gauthier; K. Whelan; J. E. L. Carlsson; J. Carlsson (Journal of Fish Biology, 2015)
This pilot study presents an environmental DNA ( eDNA ) assay for sea lamprey Petromyzon marinus and brown trout Salmo trutta , two species of economic and conservation importance in the Republic of Ireland. The results demonstrate the effectiveness of eDNA for assessing presence of low‐abundance taxa (here, P. marinus ) for environmental managers, and they highlight the potential for assessing relative abundance of rare or invasive freshwater species.

Erratum to: The somatic autosomal mutation matrix in cancer genomes - Nuri A. Temiz; Duncan E. Donohue; Albino Bacolla; Karen M. Vasquez; David N. Cooper; Uma Mudunuri; Joseph Ivanic; Regina Z. Cer; Ming Yi; Robert M. Stephens; Jack R. Collins; Brian T. Luke (Human Genetics, 2015)

The somatic autosomal mutation matrix in cancer genomes - Nuri A. Temiz; Duncan E. Donohue; Albino Bacolla; Karen M. Vasquez; David N. Cooper; Uma Mudunuri; Joseph Ivanic; Regina Z. Cer; Ming Yi; Robert M. Stephens; Jack R. Collins; Brian T. Luke (Human Genetics, 2015)

Anthropogenic nitrogen deposition predicts local grassland primary production worldwide - Carly J. Stevens; Eric M. Lind; Yann Hautier; W. Stanley Harpole; Elizabeth T. Borer; Sarah Hobbie; Eric W. Seabloom; Laura Ladwig; Jonathan D. Bakker; Chengjin Chu; Scott Collins; Kendi F. Davies; et al. (Ecology, 2015)
Humans dominate many important Earth system processes including the nitrogen (N) cycle. Atmospheric N deposition affects fundamental processes such as carbon cycling, climate regulation, and biodiversity, and could result in changes to fundamental Earth system processes such as primary production. Both modelling and experimentation have suggested a role for anthropogenically altered N deposition in increasing productivity, nevertheless, current understanding of the relative strength of N deposition with respect to other controls on production such as edaphic conditions and climate is limited. Here we use an international multiscale data set to show that atmospheric N deposition is positively correlated to aboveground net primary production (ANPP) observed at the 1‐m 2 level across a wide range of herbaceous ecosystems. N deposition was a better predictor than climatic drivers and local soil conditions, explaining 16% of observed variation in ANPP globally with an increase of 1 kg N·ha −1 ·yr −1 increasing ANPP by 3%. Soil pH explained 8% of observed variation in ANPP while climatic drivers showed no significant relationship. Our results illustrate that the incorporation of global N deposition patterns in Earth system models are likely to substantially improve estimates of primary production in herbaceous systems. In herbaceous systems across the world, humans appear to be partially driving local ANPP through impacts on the N cycle.

Climatic controls of aboveground net primary production in semi-arid grasslands along a latitudinal gradient portend low sensitivity to warming - Whitney Mowll; Dana M. Blumenthal; Karie Cherwin; Anine Smith; Amy J. Symstad; Lance T. Vermeire; Scott L. Collins; Melinda D. Smith; Alan K. Knapp (Oecologia, 2015)

Global environmental change and the nature of aboveground net primary productivity responses: insights from long-term experiments - Melinda D. Smith; Kimberly J. La Pierre; Scott L. Collins; Alan K. Knapp; Katherine L. Gross; John E. Barrett; Serita D. Frey; Laura Gough; Robert J. Miller; James T. Morris; Lindsey E. Rustad; John Yarie (Oecologia, 2015)

Songbirds as sentinels of mercury in terrestrial habitats of eastern North America - Allyson K. Jackson; David C. Evers; Evan M. Adams; Daniel A. Cristol; Collin Eagles-Smith; Samuel T. Edmonds; Carrie E. Gray; Bart Hoskins; Oksana P. Lane; Amy Sauer; Timothy Tear (Ecotoxicology, 2015)

Climate influences on water and sediment properties of Genovesa Crater Lake, Galápagos - Jessica L. Conroy; Diane M. Thompson; Aaron Collins; Jonathan T. Overpeck; Mark B. Bush; Julia E. Cole (Journal of Paleolimnology, 2014)

Brain activation during neurocognitive testing using functional near-infrared spectroscopy in patients following concussion compared to healthy controls - A. P. Kontos; T. J. Huppert; N. H. Beluk; R. J. Elbin; L. C. Henry; J. French; S. M. Dakan; M. W. Collins (Brain Imaging and Behavior, 2014)

Effects of monsoon precipitation variability on the physiological response of two dominant C4 grasses across a semiarid ecotone - Michell L. Thomey; Scott L. Collins; Michael T. Friggens; Renee F. Brown; William T. Pockman (Oecologia, 2014)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

On-line stable isotope gas exchange reveals an inducible but leaky carbon concentrating mechanism in Nannochloropsis salina - David T. Hanson; Aaron M. Collins; Howland D. T. Jones; John Roesgen; Samuel Lopez-Nieves; Jerilyn A. Timlin (Photosynthesis Research, 2014)

Vocal Activity as a Low Cost and Scalable Index of Seabird Colony Size - ABRAHAM L. BORKER; MATTHEW W. MCKOWN; JOSHUA T. ACKERMAN; COLLIN A. EAGLES‐SMITH; BERNIE R. TERSHY; DONALD A. CROLL (Conservation Biology, 2014)
Although wildlife conservation actions have increased globally in number and complexity, the lack of scalable, cost‐effective monitoring methods limits adaptive management and the evaluation of conservation efficacy. Automated sensors and computer‐aided analyses provide a scalable and increasingly cost‐effective tool for conservation monitoring. A key assumption of automated acoustic monitoring of birds is that measures of acoustic activity at colony sites are correlated with the relative abundance of nesting birds. We tested this assumption for nesting Forster's terns ( Sterna forsteri ) in San Francisco Bay for 2 breeding seasons. Sensors recorded ambient sound at 7 colonies that had 15–111 nests in 2009 and 2010. Colonies were spaced at least 250 m apart and ranged from 36 to 2,571 m 2 . We used spectrogram cross‐correlation to automate the detection of tern calls from recordings. We calculated mean seasonal call rate and compared it with mean active nest count at each colony. Acoustic activity explained 71% of the variation in nest abundance between breeding sites and 88% of the change in colony size between years. These results validate a primary assumption of acoustic indices; that is, for terns, acoustic activity is correlated to relative abundance, a fundamental step toward designing rigorous and scalable acoustic monitoring programs to measure the effectiveness of conservation actions for colonial birds and other acoustically active wildlife. La Actividad Vocal como un Índice Escalable y de Bajo Costo del Tamaño de Colonia de las Aves Marinas

Development and characterization of 15 polymorphic microsatellite markers for North Pacific albatrosses using paired-end Illumina shotgun sequencing - Luis D. Hernandez; Zachary T. Lounsberry; Paul W. Collins; Robert W. Henry; Seth D. Newsome; Benjamin N. Sacks (Conservation Genetics Resources, 2014)

Health of white sucker within the St. Louis River area of concern associated with habitat usage as assessed using stable isotopes - V. S. Blazer; J. Hoffman; H. L. Walsh; R. P. Braham; C. Hahn; P. Collins; Z. Jorgenson; T. Ledder (Ecotoxicology, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Isolation and characterization of 29 polymorphic microsatellite markers for the endangered Atlantic goliath grouper (Epinephelus itajara), and the Pacific goliath grouper (E. quinquefasciatus) - Seifu Seyoum; Michael D. Tringali; Brandon L. Barthel; Cecilia Puchulutegui; Michelle C. Davis; Angela B. Collins; Matthew T. Craig (Conservation Genetics Resources, 2013)

Effects of experimental rainfall manipulations on Chihuahuan Desert grassland and shrubland plant communities - Selene Báez; Scott L. Collins; William T. Pockman; Jennifer E. Johnson; Eric E. Small (Oecologia, 2013)

Patterns of diversity and adaptation in Glomeromycota from three prairie grasslands - Baoming Ji; Catherine A. Gehring; Gail W. T. Wilson; R. M. Miller; Lluvia Flores‐Rentería; Nancy Collins Johnson (Molecular Ecology, 2013)
Arbuscular mycorrhizal ( AM ) fungi are widespread root symbionts that often improve the fitness of their plant hosts. We tested whether local adaptation in mycorrhizal symbioses would shape the community structure of these root symbionts in a way that maximizes their symbiotic functioning. We grew a native prairie grass ( A ndropogon gerardii) with all possible combinations of soils and AM fungal inocula from three different prairies that varied in soil characteristics and disturbance history (two native prairie remnants and one recently restored). We identified the AM fungi colonizing A . gerardii roots using PCR amplification and cloning of the small subunit r RNA gene. We observed 13 operational taxonomic units ( OTU s) belonging to six genera in three families. Taxonomic richness was higher in the restored than the native prairies with one member of the G igaspora dominating the roots of plants grown with inocula from native prairies. Inoculum source and the soil environment influenced the composition of AM fungi that colonized plant roots. Correspondingly, host plants and AM fungi responded significantly to the soil–inoculum combinations such that home fungi often had the highest fitness and provided the greatest benefit to A . gerardii . Similar patterns were observed within the soil–inoculum combinations originating from two native prairies, where five sequence types of a single G igaspora OTU were virtually the only root colonizers. Our results indicate that indigenous assemblages of AM fungi were adapted to the local soil environment and that this process occurred both at a community scale and at the scale of fungal sequence types within a dominant OTU .

Dynamic Conservation of Forest Genetic Resources in 33 European Countries - FRANÇOIS LEFÈVRE; JARKKO KOSKELA; JASON HUBERT; HOJKA KRAIGHER; ROMAN LONGAUER; DITTE C. OLRIK; SILVIO SCHÜLER; MICHELE BOZZANO; PARASKEVI ALIZOTI; REMIGIJUS BAKYS; CATHLEEN BALDWIN; DALIBOR BALLIAN; et al. (Conservation Biology, 2013)
Dynamic conservation of forest genetic resources (FGR) means maintaining the genetic diversity of trees within an evolutionary process and allowing generation turnover in the forest. We assessed the network of forests areas managed for the dynamic conservation of FGR (conservation units) across Europe (33 countries). On the basis of information available in the European Information System on FGR (EUFGIS Portal), species distribution maps, and environmental stratification of the continent, we developed ecogeographic indicators, a marginality index, and demographic indicators to assess and monitor forest conservation efforts. The pan‐European network has 1967 conservation units, 2737 populations of target trees, and 86 species of target trees. We detected a poor coincidence between FGR conservation and other biodiversity conservation objectives within this network. We identified 2 complementary strategies: a species‐oriented strategy in which national conservation networks are specifically designed for key target species and a site‐oriented strategy in which multiple‐target units include so‐called secondary species conserved within a few sites. The network is highly unbalanced in terms of species representation, and 7 key target species are conserved in 60% of the conservation units. We performed specific gap analyses for 11 tree species, including assessment of ecogeographic, demographic, and genetic criteria. For each species, we identified gaps, particularly in the marginal parts of their distribution range, and found multiple redundant conservation units in other areas. The Mediterranean forests and to a lesser extent the boreal forests are underrepresented. Monitoring the conservation efficiency of each unit remains challenging; however, Conservación Dinámica de Recursos Genéticos Forestales en 33 Países Europeos

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Dissecting the dimerization motif of Enterococcus hirae’s Zn(II)CopY - Tyler C. Collins; Charles T. Dameron (JBIC Journal of Biological Inorganic Chemistry, 2012)

Eosinophilic gastrointestinal diseases—clinically diverse and histopathologically confounding - Seema Aceves; Ikuo Hirano; Glenn T. Furuta; Margaret H. Collins (Seminars in Immunopathology, 2012)

Vision in elasmobranchs and their relatives: 21st century advances - T. J. Lisney; S. M. Theiss; S. P. Collin; N. S. Hart (Journal of Fish Biology, 2012)
This review identifies a number of exciting new developments in the understanding of vision in cartilaginous fishes that have been made since the turn of the century. These include the results of studies on various aspects of the visual system including eye size, visual fields, eye design and the optical system, retinal topography and spatial resolving power, visual pigments, spectral sensitivity and the potential for colour vision. A number of these studies have covered a broad range of species, thereby providing valuable information on how the visual systems of these fishes are adapted to different environmental conditions. For example, oceanic and deep‐sea sharks have the largest eyes amongst elasmobranchs and presumably rely more heavily on vision than coastal and benthic species, while interspecific variation in the ratio of rod and cone photoreceptors, the topographic distribution of the photoreceptors and retinal ganglion cells in the retina and the spatial resolving power of the eye all appear to be closely related to differences in habitat and lifestyle. Multiple, spectrally distinct cone photoreceptor visual pigments have been found in some batoid species, raising the possibility that at least some elasmobranchs are capable of seeing colour, and there is some evidence that multiple cone visual pigments may also be present in holocephalans. In contrast, sharks appear to have only one cone visual pigment. There is evidence that ontogenetic changes in the visual system, such as changes in the spectral transmission properties of the lens, lens shape, focal ratio, visual pigments and spatial resolving power, allow elasmobranchs to adapt to environmental changes imposed by habitat shifts and niche expansion. There are, however, many aspects of vision in these fishes that are not well understood, particularly in the holocephalans. Therefore, this review also serves to highlight and stimulate new research in areas that still require significant attention.

Assessing the potential for post‐copulatory sexual selection in elasmobranchs - J. L. Fitzpatrick; R. M. Kempster; T. S. Daly‐Engel; S. P. Collin; J. P. Evans (Journal of Fish Biology, 2012)
This review highlights the potential role that post‐copulatory sexual selection plays in elasmobranch reproductive systems and the utility of this group to further understanding of evolutionary responses to the post‐copulatory processes of sperm competition and cryptic female choice. The growing genetic evidence for female multiple mating (polyandry) in elasmobranchs is summarized. While polyandry appears to be common in this group, rates of multiple paternity are highly variable between species suggesting that there is large variance in the strength of post‐copulatory sexual selection among elasmobranchs. Possible adaptations of traits important for post‐copulatory sexual selection are then considered. Particular emphasis is devoted to explore the potential for sperm competition and cryptic female choice to influence the evolution of testes size, sperm morphology, genital morphology and sperm storage organs. Finally, it is argued that future work should take advantage of the wealth of information on these reproductive traits already available in elasmobranchs to gain a better understanding of how post‐copulatory sexual selection operates in this group.

Precipitation variability and fire influence the temporal dynamics of soil CO 2 efflux in an arid grassland - Rodrigo Vargas; Scott L. Collins; Michell L. Thomey; Jennifer E. Johnson; Renee F. Brown; Donald O. Natvig; Michael T. Friggens (Global Change Biology, 2012)
Climate models suggest that extreme rainfall events will become more common with increased atmospheric warming. Consequently, changes in the size and frequency of rainfall will influence biophysical drivers that regulate the strength and timing of soil CO 2 efflux – a major source of terrestrial carbon flux. We used a rainfall manipulation experiment during the summer monsoon season ( J uly– S eptember) to vary both the size and frequency of precipitation in an arid grassland 2 years before and 2 years after a lightning‐caused wildfire. Soil CO 2 efflux rates were always higher under increased rainfall event size than under increased rainfall event frequency, or ambient precipitation. Although fire reduced soil CO 2 efflux rates by nearly 70%, the overall responses to rainfall variability were consistent before and after the fire. The overall sensitivity of soil CO 2 efflux to temperature ( Q 10 ) converged to 1.4, but this value differed somewhat among treatments especially before the fire. Changes in rainfall patterns resulted in differences in the periodicity of soil CO 2 efflux with strong signals at 1, 8, and 30 days. Increased rainfall event size enhanced the synchrony between photosynthetically active radiation and soil CO 2 efflux over the growing season before and after fire, suggesting a change in the temporal availability of substrate pools that regulate the temporal dynamics and magnitude of soil CO 2 efflux. We conclude that arid grasslands are capable of rapidly increasing and maintaining high soil CO 2 efflux rates in response to increased rainfall event size more than increased rainfall event frequency both before and after a fire. Therefore, the amount and pattern of multiple rain pulses over the growing season are crucial for understanding CO 2 dynamics in burned and unburned water‐limited ecosystems.

Effects of pramipexole on the reinforcing effectiveness of stimuli that were previously paired with cocaine reinforcement in rats - Gregory T. Collins; Alyssa R. Cunningham; Jianyong Chen; Shaomeng Wang; Amy H. Newman; James H. Woods (Psychopharmacology, 2012)

Classification, Characterisation, and Use of Small Wetlands in East Africa - Nomé Sakané; Miguel Alvarez; Mathias Becker; Beate Böhme; Collins Handa; Hellen W. Kamiri; Matthias Langensiepen; Gunter Menz; Salome Misana; Neema G. Mogha; Bodo Maria Möseler; Emiliana J. Mwita; et al. (Wetlands, 2011)

Genotoxicity in Atlantic killifish (Fundulus heteroclitus) from a PAH-contaminated Superfund site on the Elizabeth River, Virginia - Dawoon Jung; Cole W. Matson; Leonard B. Collins; Geoff Laban; Heather M. Stapleton; John W. Bickham; James A. Swenberg; Richard T. Di Giulio (Ecotoxicology, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

An investigation of Clostridium species present in nutraceutical preparations of Arthrospira platensis (Spirulina) for human consumption - Dirk T. Hoekstra; Heinrich Volschenk; Michelle Collins; Lynn D. McMaster (Journal of Applied Phycology, 2011)

Behavioral sensitization to cocaine in rats: evidence for temporal differences in dopamine D3 and D2 receptor sensitivity - Gregory T. Collins; Yen Nhu-Thi Truong; Beth Levant; Jianyong Chen; Shaomeng Wang; James H. Woods (Psychopharmacology, 2011)

Major and trace element distributions around active volcanic vents determined by analyses of grasses: implications for element cycling and bio-monitoring - R. S. Martin; T. A. Mather; D. M. Pyle; J. A. Day; M. L. I. Witt; S. J. Collins; R. G. Hilton (Bulletin of Volcanology, 2010)

The hydrochemistry of groundwater in the Densu River Basin, Ghana - Joseph Richmond Fianko; Dickson Adomako; Shiloh Osae; Samuel Ganyaglo; Benony K. Kortatsi; Collins K. Tay; Eric T. Glover (Environmental Monitoring and Assessment, 2010)

The role of geomorphology in evaluating remediation options for floodplain wetlands: the case of Ramsar-listed Seekoeivlei, eastern South Africa - T. S. McCarthy; S. Tooth; D. C. Kotze; N. B. Collins; G. Wandrag; T. Pike (Wetlands Ecology and Management, 2010)

Validation and Application of a Method for the Determination of Total Chromium in Rat Tissues by Inductively Coupled Plasma Mass Spectrometry - Keith E. Levine; Matthew D. Stout; Glenn T. Ross; Amal S. Essader; Frank X. Weber; Peter M. Grohse; Reshan A. Fernando; Lisa S. Milstein; Michelle J. Hooth; Bradley J. Collins (Archives of Environmental Contamination and Toxicology, 2010)

Organochlorine and PBDE Concentrations in Relation to Cytochrome P450 Activity in Livers of Forster’s Terns (Sterna forsteri) and Caspian Terns (Hydroprogne caspia), in San Francisco Bay, California - Garth Herring; Joshua T. Ackerman; Collin A. Eagles-Smith; Terrence L. Adelsbach; Mark J. Melancon; Katie R. Stebbins; David J. Hoffman (Archives of Environmental Contamination and Toxicology, 2010)

A meta‐analysis of context‐dependency in plant response to inoculation with mycorrhizal fungi - Jason D. Hoeksema; V. Bala Chaudhary; Catherine A. Gehring; Nancy Collins Johnson; Justine Karst; Roger T. Koide; Anne Pringle; Catherine Zabinski; James D. Bever; John C. Moore; Gail W. T. Wilson; John N. Klironomos; et al. (Ecology Letters, 2010)
Ecology Letters (2010) 13: 394–407 Abstract Mycorrhizal fungi influence plant growth, local biodiversity and ecosystem function. Effects of the symbiosis on plants span the continuum from mutualism to parasitism. We sought to understand this variation in symbiotic function using meta‐analysis with information theory‐based model selection to assess the relative importance of factors in five categories: (1) identity of the host plant and its functional characteristics, (2) identity and type of mycorrhizal fungi (arbuscular mycorrhizal vs. ectomycorrhizal), (3) soil fertility, (4) biotic complexity of the soil and (5) experimental location (laboratory vs. field). Across most subsets of the data, host plant functional group and N‐fertilization were surprisingly much more important in predicting plant responses to mycorrhizal inoculation (‘plant response’) than other factors. Non‐N‐fixing forbs and woody plants and C 4 grasses responded more positively to mycorrhizal inoculation than plants with N‐fixing bacterial symbionts and C 3 grasses. In laboratory studies of the arbuscular mycorrhizal symbiosis, plant response was more positive when the soil community was more complex. Univariate analyses supported the hypothesis that plant response is most positive when plants are P‐limited rather than N‐limited. These results emphasize that mycorrhizal function depends on both abiotic and biotic context, and have implications for plant community theory and restoration ecology.

A comprehensive resequence analysis of the KLK15–KLK3–KLK2 locus on chromosome 19q13.33 - Hemang Parikh; Zuoming Deng; Meredith Yeager; Joseph Boland; Casey Matthews; Jinping Jia; Irene Collins; Ariel White; Laura Burdett; Amy Hutchinson; Liqun Qi; Jennifer A. Bacior; et al. (Human Genetics, 2010)

How many Eurasian badgers Meles meles L. are there in the Republic of Ireland? - D. P. Sleeman; J. Davenport; S. J. More; T. A. Clegg; J. D. Collins; S. W. Martin; D. H. Williams; J. M. Griffin; I. O’Boyle (European Journal of Wildlife Research, 2009)

Linking above‐ and belowground responses to global change at community and ecosystem scales - ANITA ANTONINKA; JULIE E. WOLF; MATTHEW BOWKER; AIMÉE T. CLASSEN; NANCY COLLINS JOHNSON (Global Change Biology, 2009)
Cryptic belowground organisms are difficult to observe and their responses to global changes are not well understood. Nevertheless, there is reason to believe that interactions among above‐ and belowground communities may mediate ecosystem responses to global change. We used grassland mesocosms to manipulate the abundance of one important group of soil organisms, arbuscular mycorrhizal (AM) fungi, and to study community and ecosystem responses to CO 2 and N enrichment. Responses of plants, AM fungi, phospholipid fatty acids and community‐level physiological profiles were measured after two growing seasons. Ecosystem responses were examined by measuring net primary production (NPP), evapotranspiration, total soil organic matter (SOM), and extractable mineral N. Structural equation modeling was used to examine the causal relationships among treatments and response variables. We found that while CO 2 and N tended to directly impact ecosystem functions (evapotranspiration and NPP, respectively), AM fungi indirectly impacted ecosystem functions by influencing the community composition of plants and other root fungi, soil fungi and soil bacteria. We found that the mycotrophic status of the dominant plant species in the mesocosms determined whether the presence of AM fungi increased or decreased NPP. Mycotrophic grasses dominated the mesocosm communities during the first growing season, and the mycorrhizal treatments had the highest NPP. In contrast, nonmycotrophic forbs were dominant during the second growing season and the mycorrhizal treatments had the lowest NPP. The composition of the plant community strongly influenced soil N, and the community composition of soil organisms strongly influenced SOM accumulation in the mesocosms. These results show how linkages between above‐ and belowground communities can determine ecosystem responses to global change.

Survival of postfledging Forster’s terns in relation to mercury exposure in San Francisco Bay - Joshua T. Ackerman; Collin A. Eagles-Smith; John Y. Takekawa; Samuel A. Iverson (Ecotoxicology, 2008)

Mercury contamination and effects on survival of American avocet and black-necked stilt chicks in San Francisco Bay - Joshua T. Ackerman; John Y. Takekawa; Collin A. Eagles-Smith; Samuel A. Iverson (Ecotoxicology, 2008)

A computational fluid dynamics study of inspiratory flow in orotracheal geometries - T. P. Collins; G. R. Tabor; P. G. Young (Medical & Biological Engineering & Computing, 2007)

Geographic variation of Weddell seal (Leptonychotes weddellii) airborne mother–pup vocalisations - K. T. Collins; J. M. Terhune (Polar Biology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Yawning and hypothermia in rats: effects of dopamine D3 and D2 agonists and antagonists - Gregory T. Collins; Amy Hauck Newman; Peter Grundt; Kenner C. Rice; Stephen M. Husbands; Cédric Chauvignac; Jianyong Chen; Shaomeng Wang; James H. Woods (Psychopharmacology, 2007)

Cold-Adapted Enzymes from Marine Antarctic Microorganisms - J-C. Marx; T. Collins; S. D’Amico; G. Feller; C. Gerday (Marine Biotechnology, 2007)

A novel locus for autosomal recessive nonsyndromic hearing impairment, DFNB63, maps to chromosome 11q13.2–q13.4 - E. Kalay; R. Caylan; A. F. Kıroglu; T. Yasar; R. W. J. Collin; J. G. A. M. Heister; J. Oostrik; C. W. R. J. Cremers; H. G. Brunner; A. Karaguzel; H. Kremer (Journal of Molecular Medicine, 2007)

Stream insect occupancy-frequency patterns and metapopulation structure - T. Heatherly; M. R. Whiles; D. J. Gibson; S. L. Collins; A. D. Huryn; J. K. Jackson; M. A. Palmer (Oecologia, 2007)

VOCAL INDIVIDUALITY OF IN‐AIR WEDDELL SEAL ( LEPTONYCHOTES WEDDELLII ) PUP “PRIMARY” CALLS - Kym T. Collins; John M. Terhune; Tracey L. Rogers; Kathryn E. Wheatley; Robert G. Harcourt (Marine Mammal Science, 2006)
As a result of selective pressures faced during lactation, vocal recognition may play a crucial role in maintaining the phocid mother–pup bond during the period of dependence. To investigate this possibility, we examined whether Weddell seal ( Leptonychotes weddellii ) pups produce individually distinctive “primary” calls. One temporal, nine fundamental frequency features, and two spectral characteristics were measured. A discriminant function analysis (DFA) of 15 Vestfold Hills pups correctly classified 52% of calls, while the cross‐validation procedure classified 29% of calls to the correct pup. A second DFA of 10 known‐age McMurdo Sound pups correctly classified 44% of “test” calls. For novel calls, the probabilities of attaining such classification rates by chance are low. The relationship between age and call stereotypy indicated that pups 2 wk and older may be more vocally distinctive. Overall, findings suggest that Weddell seal pup “primary” calls are moderately distinctive and only exhibit sufficient stereotypy to aid maternal recognition by approximately two weeks of age.

Brain morphology in large pelagic fishes: a comparison between sharks and teleosts - T. J. Lisney; S. P. Collin (Journal of Fish Biology, 2006)
A quantitative comparison was made of both relative brain size (encephalization) and the relative development of five brain area of pelagic sharks and teleosts. Two integration areas (the telencephalon and the corpus cerebellum) and three sensory brain areas (the olfactory bulbs, optic tectum and octavolateralis area, which receive primary projections from the olfactory epithelium, eye and octavolateralis senses, respectively), in four species of pelagic shark and six species of pelagic teleost were investigated. The relative proportions of the three sensory brain areas were assessed as a proportion of the total ‘sensory brain’, while the two integration areas were assessed relative to the sensory brain. The allometric analysis of relative brain size revealed that pelagic sharks had larger brains than pelagic teleosts. The volume of the telencephalon was significantly larger in the sharks, while the corpus cerebellum was also larger and more heavily foliated in these animals. There were also significant differences in the relative development of the sensory brain areas between the two groups, with the sharks having larger olfactory bulbs and octavolateralis areas, whilst the teleosts had larger optic tecta. Cluster analysis performed on the sensory brain areas data confirmed the differences in the composition of the sensory brain in sharks and teleosts and indicated that these two groups of pelagic fishes had evolved different sensory strategies to cope with the demands of life in the open ocean.

Mitochondrial polymorphisms and susceptibility to type 2 diabetes-related traits in Finns - Karen L. Mohlke; Anne U. Jackson; Laura J. Scott; Erin C. Peck; Yong D. Suh; Peter S. Chines; Richard M. Watanabe; Thomas A. Buchanan; Karen N. Conneely; Michael R. Erdos; Narisu Narisu; Sareena Enloe; et al. (Human Genetics, 2005)

Vegetation, Invertebrate, and Wildlife Community Rankings and Habitat Analysis of Mitigation Wetlands in West Virginia - Collin K. Balcombe; James T. Anderson; Ronald H. Fortney; Walter S. Kordek (Wetlands Ecology and Management, 2005)

The Novel and Endemic Pathogen Hypotheses: Competing Explanations for the Origin of Emerging Infectious Diseases of Wildlife - LARA J. RACHOWICZ; JEAN‐MARC HERO; ROSS A. ALFORD; JOHN W. TAYLOR; JESS A.T. MORGAN; VANCE T. VREDENBURG; JAMES P. COLLINS; CHERYL J. BRIGGS (Conservation Biology, 2005)
Chytridiomycosis, caused by the fungal pathogen Batrachochytrium dendrobatidis , is an emerging infectious disease implicated in declines of amphibian populations around the globe. An emerging infectious disease is one that has recently been discovered; has recently increased in incidence, geography, or host range; or is newly evolved. For any given outbreak of an emerging disease, it is therefore possible to state two hypotheses regarding its origin. The novel pathogen hypothesis states that the disease has recently spread into new geographic areas, whereas the endemic pathogen hypothesis suggests that it has been present in the environment but recently has increased in host range or pathogenicity. Distinguishing between these hypotheses is important, because the conservation measures needed to slow or stop the spread of a novel pathogen are likely to differ from those needed to prevent outbreaks of an endemic pathogen. Population genetics may help discriminate among the possible origins of an emerging disease. Current evidence suggests chytridiomycosis may be a novel pathogen being spread worldwide by carriers; until we know how much genetic variation to expect in an endemic strain, however, we cannot yet conclude that B. dendrobatidis is a novel pathogen.

Aquatic macroinvertebrate assemblages in mitigated and natural wetlands - Collin K. Balcombe; James T. Anderson; Ronald H. Fortney; Walter S. Kordek (Hydrobiologia, 2005)

Antitumor and Anti-Pneumocystis Carinii Activities of Novel Bisbenzamidines - Jean Jacques Vanden Eynde; Annie Mayence; Melissa T. Johnson; Tien L. Huang; Margaret S. Collins; Sandra Rebholz; Peter D. Walzer; Melanie T. Cushion; Isaac O. Donkor (Medicinal Chemistry Research, 2005)

A comparison of plant communities in mitigation and reference wetlands in the mid-appalachians - Collin K. Balcombe; James T. Anderson; Ronald H. Fortney; James S. Rentch; William N. Grafton; Walter S. Kordek (Wetlands, 2005)

Carbohydrate Distribution in Stalks and Ears of Sweet Maize with Different Endosperm Genotypes - V. M. Russo; J. K. Collins; P. Perkins-Veazie; T. Smith (Cereal Research Communications, 2004)

The role of the defective interfering particle DI9c in mucosal disease in cattle - M. Stokstad; M. Collins; R. Srby; P. Barboni; G. Meyers; T. Lken; J. Brownlie (Archives of Virology, 2004)

Sequence Analysis of the Washington/1964 strain of Human Parainfluenza Virus Type 1 (HPIV1) and Recovery and Characterization of Wild Type Recombinant HPIV1 Produced by Reverse Genetics - J. T. Newman; S. R. Surman; J. M. Riggs; Chris T. Hansen; P. L. Collins; B. R. Murphy; M.H. Skiadopoulos (Virus Genes, 2003)

The Activation Energy at T g and the Fragility Index of Indomethacin, Predicted from the Influence of the Heating Rate on the Temperature Position and on the Intensity of Thermally Stimulated Depolarization Current Peak - Joaquim J. Moura Ramos; Natália T. Correia; Raquel Taveira-Marques; George Collins (Pharmaceutical Research, 2002)

Sequence Analysis of the Washington/1964 Strain of Human Parainfluenza Virus Type 1 (HPIV1) and Recovery and Characterization of Wild-Type Recombinant HPIV1 Produced by Reverse Genetics - Jason T. Newman; Sonja R. Surman; Jeffrey M. Riggs; Chris T. Hansen; Peter L. Collins; Brian R. Murphy; Mario H. Skiadopoulos (Virus Genes, 2002)

Molecular Mobility and Fragility in Indomethacin: A Thermally Stimulated Depolarization Current Study - Natália T. Correia; Joaquim J. Moura Ramos; Marc Descamps; George Collins (Pharmaceutical Research, 2001)

Trends in extreme daily rainfall and temperature in Southeast Asia and the South Pacific: 1961–1998 - M.J. Manton; P.M. Della‐Marta; M.R. Haylock; K.J. Hennessy; N. Nicholls; L.E. Chambers; D.A. Collins; G. Daw; A. Finet; D. Gunawan; K. Inape; H. Isobe; et al. (International Journal of Climatology, 2001)
Trends in extreme daily temperature and rainfall have been analysed from 1961 to 1998 for Southeast Asia and the South Pacific. This 38‐year period was chosen to optimize data availability across the region. Using high‐quality data from 91 stations in 15 countries, significant increases were detected in the annual number of hot days and warm nights, with significant decreases in the annual number of cool days and cold nights. These trends in extreme temperatures showed considerable consistency across the region. Extreme rainfall trends were generally less spatially coherent than were those for extreme temperature. The number of rain days (with at least 2 mm of rain) has decreased significantly throughout Southeast Asia and the western and central South Pacific, but increased in the north of French Polynesia, in Fiji, and at some stations in Australia. The proportion of annual rainfall from extreme events has increased at a majority of stations. The frequency of extreme rainfall events has declined at most stations (but not significantly), although significant increases were detected in French Polynesia. Trends in the average intensity of the wettest rainfall events each year were generally weak and not significant. Copyright © 2001 Royal Meteorological Society

Application methodology of ca and/or fumigation including use of carbon dioxide under increased pressure - C. J. Waterford; P. P. Asher; M. G. Andrada; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; P. V. Herrera; M. G. Andrada; Ma. Elvira M. Martinez; R. P. Estigoy; P. Williams; R. Ryan; R. Cavasin; et al. (Phytoparasitica, 2001)

Potential threats to conventional ca and/or fumigation (regulatory, insect resistance) - K. A. Mills; PJ. Collins; G. J. Daglish; M. K. Nayak; P. J. Collins; Cao Yang; Wang Dianxuan; T. A. Lambkin (Phytoparasitica, 2001)

Embryogenic response of multiple soybean [Glycine max (L.) merr.] cultivars across three locations - C. A. Meurer; R. D. Dinkins; C. T. Redmond; K. P. McAllister; D. T. Tucker; D. R. Walker; W. A. Parrott; H. N. Trick; J. S. Essig; H. M. Frantz; J. J. Finer; G. B. Collins (In Vitro Cellular & Developmental Biology - Plant, 2001)

Characterisation of marine and lacustrine sediments in a drowned thermokarst embayment, Richards Island, Beaufort Sea, Canada - S. Solomon; P. J. Mudie; R. Cranston; T. Hamilton; S. A. Thibaudeau; E. S. Collins (International Journal of Earth Sciences, 2000)

Foraging under the risk of cannibalism leads to divergence in body size among tiger salamander larvae - R. E. Ziemba; M. T. Myers; J. P. Collins (Oecologia, 2000)

Annual cycle of energy allocation to growth and reproduction of yellow perch - B. A. Henderson; T. Trivedi; N. Collins (Journal of Fish Biology, 2000)
Growth (length, weight) of yellow perch Perca flavescens in western and west‐central Lake Erie began between June and July, possibly reaching asymptotic size by early winter. Energy density (kJ g −1 ) of somatic tissue increased markedly from June to September, then declined to low levels by the following spring. Consequently, energy mass (kJ) of somatic tissue increased to September and then declined slowly until March. Ovarian growth began in October, and the size of the ovaries was maximal in April, just before spawning in May. The energy density of ovaries, however, increased to a peak in December, and then declined. The increase in ovary size in the winter, therefore, resulted largely from an allocation of tissue of low energy density. Fecundity and gonad size were correlated with somatic and gonadal energy density. A bioenergetics model was used to describe the monthly allocations of energy to respiration, growth, excretion, and reproduction. Most direct reproductive costs (80%) were incurred from September to December, corresponding to the cycle in the activity of the liver. Energy acquired in the early summer may be critical for determining maturation, fecundity, and egg quality. From 1978 to 1990,

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Calretinin-immunoreactive nerves in the uterus, pelvic autonomic ganglia, lumbosacral dorsal root ganglia and lumbosacral spinal cord - R.E. Papka; J. Collins; T. Copelin; K. Wilson (Cell and Tissue Research, 1999)

Surface Water Transport of Lead at a Shooting Range - J. R. Craig; J. D. Rimstidt; C. A. Bonnaffon; T. K. Collins; P. F. Scanlon (Bulletin of Environmental Contamination and Toxicology, 1999)

The role of food availability in regulating reproductive development in female golden perch - A. L. Collins; T. A. Anderson (Journal of Fish Biology, 1999)
At a time of the year when female golden perch Macquaria ambigua are not normally reproductively active, they were either fed daily to satiety (Fed), starved for 150 days (S150), or starved for 150 days then fed to satiety for 30 or 60 days (S150/F30 or S150/F60). Fish showed rapid growth and increased food conversion efficiency upon re‐feeding relative to Fed animals. The hepatosomatic indices were not significantly different between Fed, S150/F30 and S150/F60 groups, but were significantly reduced in S150 animals. The gonadosomatic indices ( I G ) for both Fed and S150 animals were not significantly different. However, the I G values for S150/F30 and S150/F60 animals of 6·74±1·22 and 7·84±1·12 were significantly elevated relative to Fed animals and approach those described for wild mature M. ambigua . Oocyte development in Fed and S150 animals did not proceed past the cortical alveoli or perinucleolar stages, respectively, but oocytes in both S150/F30 and S150/F60 animals had undergone vitellogenesis and were close to being mature. The concentration of oestradiol and testosterone in the plasma of S150/F30 and S150/F60 animals increased in accordance with the proposed role of these hormones in teleost reproductive cycles. The reproductive response of M. ambigua to starvation and re‐feeding is well suited to reproductive success in temperate Australian rivers where food availability is unpredictable.

The effects of stochastic galvanic vestibular stimulation on human postural sway - A. E. Pavlik; J. T. Inglis; M. Lauk; L. Oddsson; J. J. Collins (Experimental Brain Research, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Characterization and localization of two forms of gonadotropin-releasing hormone (GnRH) in the spinal cord of the frog Rana ridibunda - Nicolas Chartrel; Françoise Collin; Yung-Sen Huang; Maïté Montero; Marie-Christine Tonon; H. J. T. Goos; Sylvie Dufour; H. Vaudry (Cell and Tissue Research, 1998)

Repeated methylphenidate treatment induces behavioral sensitization and decreases protein kinase A and dopamine-stimulated adenylyl cyclase activity in the dorsal striatum - C. A. Crawford; S. A. McDougall; T. L. Meier; R. L. Collins; J. B. Watson (Psychopharmacology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Molecular analysis of interspecific and intergeneric relationships of Banksia using RAPDs and non-coding chloroplast DNA sequences - T. L. Maguire; J. G. Conran; G. G. Collins; M. Sedgley (Theoretical and Applied Genetics, 1997)

The influence of changes in food availability on the activities of key degradative and metabolic enzymes in the liver and epaxial muscle of the golden perch - A. L. Collins; T. A. Anderson (Journal of Fish Biology, 1997)
This study investigated the influence of feeding frequency on the activities of important degradative enzymes and potentially rate‐limiting enzymes in glycolysis and gluconeogenesis in the liver and white epaxial muscle of Macquaria ambigua . Adult animals were either fed daily to satiety (fed), deprived of food for up to 180 days (starved), or starved for 150 days then fed daily to satiety for 30 days (starved/fed). The activities of lipolytic, glycogenolytic and glycolytic enzymes in the livers of starved fish were maintained as long as liver energy stores were available, but became significantly reduced following their exhaustion indicating a decline in metabolism in response to prolonged starvation. The response of epaxial muscle metabolism to changes in food availability was different to that of the liver, as no significant change in the activities of muscle lipolytic or glycogenolytic enzymes were observed in response to starvation. Muscle tissue metabolism was reduced after 60–90 days of starvation, but then returned to prestarvation levels.

Microgeographic structure of Anopheles gambiae in western Kenya based on mtDNA and microsatellite loci - T. Lehmann; N. J. Besansky; W. A. Hawley; T. G. Fahey; L. Kamau; F. H. Collins (Molecular Ecology, 1997)
The population genetic structure of the Anopheles gambiae in western Kenya was studied using length variation at five microsatellite loci and sequence variation in a 648‐nt mtDNA fragment. Mosquitoes were collected from houses in villages spanning up to 50 km distance, The following questions were answered, (i) Are mosquitoes in a house more related genetically to each other than mosquitoes between houses? (ii) What degree of genetic differentiation occurs on these geographical scales? (iii) How consistent are the results obtained with both types of genetic markers? At the house level, no differentiation was detected by F ST and R ST , and the band sharing index test revealed no significant associations of alleles across loci. Likewise, indices of kinship based on mtDNA haplotypes in houses were even lower than in the pooled sample. Therefore, the hypothesis that mosquitoes in a house are more related genetically was rejected. At increasing geographical scales, microsatellite allele distributions were similar among all population samples and no subdivision of the gene pool was detected by F ST or R ST . Likewise, estimates of haplotype divergence of mtDNA between populations were not higher than the within population estimates, and mtDNA‐based F ST values were not significantly different from zero. That sequence variation in mtDNA provided matching results with microsatellite loci (while high genetic variation was observed in all loci), suggested that this pattern represents the whole genome. The minimum area associated with a deme of A. gambiae in western Kenya is therefore larger than 50 km in diameter.

A medium-density genetic linkage map of the bovine genome - W. Barendse; D. Vaiman; S. J. Kemp; Y. Sugimoto; S. M. Armitage; J. L. Williams; H. S. Sun; A. Eggen; M. Agaba; S. A. Aleyasin; M. Band; M. D. Bishop; et al. (Mammalian Genome, 1997)

Desulfitobacterium sp. strain PCE1, an anaerobic bacterium that can grow by reductive dechlorination of tetrachloroethene or ortho -chlorinated phenols - J. Gerritse; Veronique Renard; T. M. Pedro Gomes; Paul A. Lawson; Matthew D. Collins; Jan C. Gottschal (Archives of Microbiology, 1996)

The detuning factor in the dynamics of interlimb rhythmic coordination - Dagmar Sternad; David Collins; M. T. Turvey (Biological Cybernetics, 1995)

Autoregulation of testicular luteinizing hormone receptors in hypogonadal (hpg/hpg) mice - A. Amador; T. Parkening; W. Beamer; A. Bartke; T. J. Collins (Biochemical Genetics, 1984)

Recovery of a Sendai virus variant with temperature-sensitive hemolytic activity from persistently infected cells from mouse brain - Arlene R. Collins; T. D. Flanagan (Archives of Virology, 1978)

Interferon production and response to exogenous interferon in two cell lines of mouse brain origin persistently infected with Sendai virus - Arlene R. Collins; T. D. Flanagan (Archives of Virology, 1977)

Staging in tubular oxygenators — Experimental results - John T. Collins; Arthur S. Palmer; Louis R. Head (Annals of Biomedical Engineering, 1973)

The mouse liver aldehyde oxidase locus (Aox) - J. G. Watson; T. J. Higgins; P. B. Collins; S. Chaykin (Biochemical Genetics, 1972)